Reinforcing film, optical member, and electronic member

By using polymers (A) and (B) with specific compositions in the adhesive layer, combined with a crosslinking agent, the problem of the transition from initial light peel strength to high adhesion strength in flexible devices is solved, achieving a balance between flexibility and reinforcing performance.

CN120981540APending Publication Date: 2025-11-18NITTO DENKO CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202480022299.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-27
Filing Date
2024-03-21
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing adhesives in flexible equipment struggle to exhibit light peelability initially and then significantly increase adhesive strength while maintaining flexibility, thus affecting the equipment's repeated bending and flexing performance.

Method used

An adhesive layer comprising polymer (A) and polymer (B) is used. Polymer (B) contains a polyorganosiloxane backbone and (meth)acrylic monomer units, while polymer (A) contains monomer units derived from nitrogen-containing monomers. By adjusting the WN/WZr ratio and the content of polymer (B), and combining it with a crosslinking agent, a transformation from easy peeling to high adhesion is achieved.

Benefits of technology

It exhibits mild peeling properties in the initial bonding stage, but the adhesion strength increases significantly in the later stage. It also has good flexibility and repeated bending and flexing performance, making it suitable for strengthening and protecting flexible equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120981540A_ABST
    Figure CN120981540A_ABST
Patent Text Reader

Abstract

Provided is a reinforcing film provided with an adhesive layer containing a polymer (A) and a polymer (B). The polymer (B) contains a monomer unit having a polyorganosiloxane skeleton and a (meth) acrylic monomer unit. The polymer (A) is an acrylic polymer containing a monomer unit derived from a nitrogen-containing monomer. The amount WN (parts by weight) of the monomer unit derived from the nitrogen-containing monomer contained in 100 parts by weight of the polymer (A) is 14 parts by weight or less. The adhesive layer further contains a zirconium-containing compound in which WZr (parts by weight) is taken as 100 parts by weight of the polymer (A), and the ratio (WN / WZr) is 4 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a reinforcing film and optical and electronic components having the reinforcing film adhered to them.

[0002] This application claims priority based on Japanese Patent Application No. 2023-050192, filed on March 27, 2023, the entire contents of which are incorporated herein by reference. Background Technology

[0003] Adhesives, in the form of adhesive sheets, are widely used in various applications such as portable electronic devices like mobile phones, smartphones, and tablet computers, as well as other electronic devices, for purposes such as bonding objects together and fixing articles to objects. For example, adhesive sheets are used as reinforcing materials (reinforcing films) to impart rigidity and impact resistance to optical components, electronic components, etc., constituting the aforementioned devices. Patent Document 1 and Patent Document 2 are cited as examples of this prior art.

[0004] In addition, in recent years, portable electronic devices that can be bent or rolled up have attracted attention, and an adhesive sheet is being developed that can be used to fix flexible devices (typically image display devices such as organic EL and liquid crystal display devices) built into such electronic devices (Patent Documents 3-6).

[0005] On the other hand, focusing on the performance of adhesives, an adhesive sheet has recently been proposed that exhibits low adhesive force in the initial stage of bonding to the substrate, followed by a significant increase in adhesive force (Patent Document 7). Using an adhesive sheet with such characteristics, it can exhibit re-applying properties (reprocessing properties) useful for suppressing misapplication and yield reduction caused by poor application before the adhesive force increases, and exhibit strong adhesion suitable for the original purpose of the adhesive sheet after the adhesive force increases.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent No. 6366199

[0009] Patent Document 2: Japanese Patent No. 6366200

[0010] Patent Document 3: Japanese Patent No. 6376271

[0011] Patent Document 4: Japanese Patent Application Publication No. 2016-108555

[0012] Patent Document 5: Japanese Patent Application Publication No. 2017-095657

[0013] Patent Document 6: Japanese Patent Application Publication No. 2017-095659

[0014] Patent Document 7: Japanese Patent No. 6373458 Summary of the Invention

[0015] The problem that the invention aims to solve

[0016] Reinforcing films can also be used in the aforementioned flexible devices. For example, in the manufacture of these flexible devices, the components constituting them are mostly thin; therefore, it is ideal to use adhesive sheets as reinforcing films to prevent adverse effects caused by device deformation or to improve operability. Flexible devices can be repeatedly bent or folded; therefore, the adhesive constituting the reinforcing film for flexible devices must possess flexibility that allows it to follow the adhered object well in such applications. Adhesives with such flexibility and reinforcing films containing such adhesives can be used in a variety of applications, including flexible devices, thus offering fewer limitations on their application scope and making them useful.

[0017] For example, for adhesives configured as described in Patent Document 7, which exhibit low adhesive strength initially followed by a significant increase in adhesive strength, it is also ideal to possess flexibility suitable for repeated bending and folding when used as a reinforcing film. One method for achieving this is, for example, to appropriately set the storage modulus of the adhesive at low temperatures. However, in adhesives designed as having increasing adhesive strength as described above, changing the storage modulus at low temperatures will affect both the initial low adhesive strength and the increased adhesive strength. For adhesives exhibiting low adhesive strength initially followed by a significant increase in adhesive strength, improving the flexibility of the adhesive is practically beneficial.

[0018] The present invention was made in view of the above circumstances, and its object is to provide a reinforcing film that exhibits mild peelability in the initial stage of adhesion to the substrate, followed by a significant increase in adhesive strength, and also possesses good flexibility. Furthermore, another object of the present invention is to provide an optical component and an electronic component to which the above-mentioned reinforcing film is adhered.

[0019] Solution for solving the problem

[0020] According to this specification, a reinforcing film is provided, comprising an adhesive layer. The adhesive layer comprises a polymer (A) and a polymer (B). The polymer (B) comprises monomer units having a polyorganosiloxane backbone and (meth)acrylic monomer units. The polymer (A) is an acrylic polymer comprising monomer units derived from nitrogen-containing monomers, and the amount of the nitrogen-containing monomer units contained in 100 parts by weight of the polymer (A) is W. NThe [parts by weight] are 14 parts by weight or less. The adhesive layer further comprises W parts by weight relative to 100 parts by weight of the polymer (A). Zr [parts by weight] of zirconium-containing compounds. The above W N [Parts by weight] relative to the above W Zr The ratio of [parts by weight] (W) N / W Zr The value is 4 or higher.

[0021] According to the reinforcing film constructed as described above, the adhesive layer comprises polymer (A) and polymer (B), wherein polymer (B) contains monomer units having a polyorganosiloxane backbone, thus exhibiting mild peelability in the initial stage of adhesion to the substrate, followed by a significant increase in adhesive strength. Furthermore, by adjusting the amount W of the aforementioned monomer units derived from nitrogen-containing monomers contained in each 100 parts by weight of polymer (A)... N The [parts by weight] are limited to 14 parts by weight or less, and the adhesive layer also exhibits flexibility suitable for repeated bending and flexing. Furthermore, the adhesive layer contains a zirconium-containing compound, and the aforementioned W... N [Parts by weight] relative to W Zr The ratio of [parts by weight] (W) N / W Zr If the value is 4 or higher, it can reduce W. N It is limited to 14 parts by weight or less, and takes into account both initial light peel and high adhesion after the adhesion increases.

[0022] In some embodiments of the disclosed technologies (including reinforcing films, optical components, electronic components, adhesives for these, and adhesive compositions for forming the adhesives, hereinafter the same), the adhesive layer comprises a crosslinking agent. By using the crosslinking agent, the cohesiveness of the adhesive layer can be appropriately adjusted. It should be noted that "comprising a crosslinking agent" here means including the crosslinking agent in its crosslinked form.

[0023] In some embodiments, the content of polymer (B) in the adhesive layer is 0.1 to 10 parts by weight relative to 100 parts by weight of polymer (A). By setting the amount of polymer (B) relative to 100 parts by weight of polymer (A) to 0.1 parts by weight or more, it is easy to obtain light peeling properties in the initial stage of adhesion. By setting the amount of polymer (B) to 10 parts by weight or less, it is easy to obtain high adhesion after the adhesion strength increases. Furthermore, by setting the amount of polymer (B) used in the above range, it is easy to balance low initial adhesion strength, high adhesion strength after the adhesion strength increases, and good flexibility (e.g., low storage modulus at low temperatures).

[0024] In some embodiments, the polymer (A) comprises monomer units derived from a monomer having a nitrogen-containing ring as the aforementioned monomer units derived from a nitrogen-containing monomer. According to the polymer (A) comprising monomer units derived from a monomer having a nitrogen-containing ring, high post-adhesion adhesion is readily obtained.

[0025] For some preferred reinforcing films, the adhesion (initial adhesion) N1 after being bonded to a polyimide film and subjected to 30 minutes at 23°C is 200 gf / 25 mm or less. Reinforcing films with an initial adhesion N1 of 200 gf / 25 mm or less exhibit good, easy-peel properties suitable for reprocessing in the initial stages of adhesion to the substrate.

[0026] For some preferred reinforcing films, the adhesion strength (post-heat adhesion strength) N2 after being bonded to a polyimide film and heated at 60°C for 1 hour followed by 30 minutes at 23°C is 1000gf / 25mm or higher. Reinforcing films with a post-heat adhesion strength N2 of 1000gf / 25mm or higher can maintain high adhesion strength after the adhesion strength increases.

[0027] For some preferred reinforcing films, the rate of increase [%) of the adhesive force N2 [gf / 25mm] after being bonded to a polyimide film and heated at 60°C for 1 hour and then at 23°C for 30 minutes is 900% or more relative to the adhesive force N1 [gf / 25mm] after being bonded to a polyimide film and then at 23°C for 30 minutes. Reinforcing films with an adhesive force increase rate (N2 / N1) of 900% or more exhibit light peelability suitable for reprocessing in the initial stage of bonding, and the adhesive force increases significantly upon subsequent heating.

[0028] In some preferred embodiments, the storage modulus (G'-) of the adhesive constituting the adhesive layer at -20°C is... 20 The energy storage modulus is below 1000 kPa. This means that adhesives with low energy storage modulus at -20°C also exhibit high flexibility suitable for repeated bending and flexing.

[0029] The reinforcing films disclosed herein are preferably used, for example, to impart rigidity and impact resistance to optical components such as polarizers and wavelength plates during processing and transportation. Therefore, according to this specification, an optical component to which any of the reinforcing films disclosed herein is adhered is provided.

[0030] Furthermore, the reinforcing film disclosed herein is also preferably used as a reinforcing film for electronic components in devices such as portable electronic devices. Therefore, according to this specification, an electronic component having any of the reinforcing films disclosed herein adhered to it is provided.

[0031] It should be noted that solutions obtained by appropriately combining the elements described in this specification may also be included within the scope of the invention for which patent protection is sought through this application. Attached Figure Description

[0032] Figure 1 This is a schematic cross-sectional view showing the structure of a reinforcing membrane according to one embodiment.

[0033] Figure 2 This is a cross-sectional view schematically showing the structure of a reinforcing membrane according to another embodiment.

[0034] Figure 3 This is a cross-sectional view schematically showing the structure of a reinforcing membrane according to another embodiment. Detailed Implementation

[0035] The preferred embodiments of the present invention will now be described. Matters necessary for carrying out the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on carrying out the invention described in this specification and common technical knowledge at the time of application. The present invention can be carried out based on the disclosures in this specification and common technical knowledge in the field.

[0036] It should be noted that in the following figures, sometimes the same reference numerals are used to describe components / parts that perform the same function, and sometimes repeated descriptions are omitted or simplified. Furthermore, the embodiments described in the figures are schematic for the purpose of clearly illustrating the invention and may not accurately represent the dimensions or scale of the actual product provided.

[0037] Furthermore, in this specification, "acrylic polymer" refers to a polymer whose polymer structure contains monomer units derived from (meth)acrylic monomers, typically meaning a polymer containing monomer units derived from (meth)acrylic monomers in a proportion exceeding 50% by weight. Additionally, a (meth)acrylic monomer refers to a monomer having at least one (meth)acryloyl group in one molecule. Here, "(meth)acryloyl" means including both an acryloyl group and a methacryloyl group. Therefore, the concept of (meth)acrylic monomers herein can include both monomers having an acryloyl group (acrylic monomers) and monomers having a methacryloyl group (methacrylic monomers). Similarly, in this specification, "(meth)acrylic acid" means including both acrylic acid and methacrylic acid, and "(meth)acrylate" means including both acrylates and methacrylates.

[0038] <Example of a reinforced membrane structure>

[0039] The reinforcing film disclosed herein has the form of an adhesive sheet, which has an adhesive surface formed by an adhesive. The adhesive sheet used as the reinforcing film is constructed by including an adhesive layer. The reinforcing film disclosed herein can be in the form of an adhesive sheet with a substrate having the aforementioned adhesive layer laminated on one or both sides of a supporting substrate, or it can be in the form of an adhesive sheet without a supporting substrate. Hereinafter, the supporting substrate will sometimes be simply referred to as "substrate".

[0040] It should be noted that, in this specification, "reinforcing film" refers to the adhesive sheet (reinforcing adhesive film) used to reinforce adhered objects as described below. The reinforcing film can be, for example, in the form of a substrate-free adhesive sheet, where a support material is adhered to one adhesive surface, and the other adhesive surface is then adhered to the adhered object to be reinforced. Therefore, it is not limited to the form of an adhesive sheet with a substrate. In this respect, it can be understood as a broader concept than the "reinforcing film" described below, which has the form of an adhesive sheet with a substrate.

[0041] The structure of the reinforcing membrane of one embodiment is schematically shown in... Figure 1 The reinforcing film 1 is configured as a single-sided adhesive sheet with a substrate, comprising: a sheet-shaped support substrate 10 having a first surface 10A and a second surface 10B; and an adhesive layer 21 disposed on the first surface 10A side. The adhesive layer 21 is fixed to the first surface 10A side of the support substrate 10. The reinforcing film 1 is used to adhere the adhesive layer 21 to the object being adhered. Figure 1 As shown, the reinforcing film 1 before use (i.e., before being adhered to the object) can be a component of a reinforcing film 100 with a release liner. This reinforcing film 100 with a release liner has a form in which the surface (adhesive surface) 21A of the adhesive layer 21 abuts against a release liner 31, which is at least on the side opposite the adhesive layer 21, forming a peelable surface (peel surface). For example, a release liner 31 can preferably be used where a release layer formed by a release agent is provided on one side of a sheet substrate (liner substrate), making that side a peelable surface. Alternatively, the release liner 31 can be omitted, and the reinforcing film 1 can be wound around a support substrate 10 with its second side 10B as the peelable surface, thereby bringing the adhesive surface 21A against the second side 10B of the support substrate 10 (roll form). When the reinforcing film 1 is adhered to the object, the second surface 10B of the release liner 31 or the support substrate 10 is peeled off from the adhesive surface 21A, and the exposed adhesive surface 21A is pressed onto the object.

[0042] The structure of the reinforcing membrane according to another embodiment is schematically shown in Figure 2The reinforcing film 2 is configured as a double-sided adhesive sheet with a substrate, comprising: a sheet-shaped support substrate 10 having a first surface 10A and a second surface 10B; an adhesive layer 21 disposed on the first surface 10A side; and an adhesive layer 22 disposed on the second surface 10B side. The adhesive layer (first adhesive layer) 21 is fixed to the first surface 10A of the support substrate 10, and the adhesive layer (second adhesive layer) 22 is fixed to the second surface 10B of the support substrate 10. The reinforcing film 2 is used to adhere the adhesive layers 21 and 22 to different parts of the adhered object. The parts to which the adhesive layers 21 and 22 are adhered can be individual parts of different components or different parts within a single component. Figure 2 As shown, the reinforcing film 2 before use can be a component of the reinforcing film 200 with a release liner. The reinforcing film 200 with a release liner has a form in which the surface of the adhesive layer 21 (first adhesive surface) 21A and the surface of the adhesive layer 22 (second adhesive surface) 22A abut against release liners 31 and 32, which respectively become release surfaces on at least one side opposite to the adhesive layers 21 and 22. As release liners 31 and 32, for example, release liners configured such that a release layer formed by a release agent is provided on one side of a sheet substrate (liner substrate), and that one side becomes a release surface, are preferably used. Alternatively, the release liner 32 can be omitted, and a release liner 31 with release surfaces on both sides can be used. This release liner is overlapped with the reinforcing film 2 and wound into a spiral shape, thereby forming a form in which the second adhesive surface 22A abuts against the back of the release liner 31 (roll form).

[0043] The structure of the reinforcing membrane according to another embodiment is schematically shown in Figure 3 The reinforcing film 3 is configured as a substrate-free double-sided adhesive sheet formed by an adhesive layer 21. The reinforcing film 3 is used to adhere a first adhesive surface 21A, formed by one surface (first surface) of the adhesive layer 21, and a second adhesive surface 21B, formed by the other surface (second surface) of the adhesive layer 21, to different parts of an object being adhered. For example... Figure 3 As shown, the reinforcing film 3 before use can be a component of the reinforcing film 300 with a release liner. The reinforcing film 300 with a release liner has a first adhesive surface 21A and a second adhesive surface 21B abutting against release liners 31 and 32, which respectively become release surfaces on at least one side opposite to the adhesive layer 21. Alternatively, the release liner 32 can be omitted, and a release liner 31 with release surfaces on both sides can be used. This release liner 31 is overlapped with the reinforcing film 3 and rolled into a spiral shape, thereby forming a reinforcing film with a release liner in which the second adhesive surface 21B abuts against the back of the release liner 31 (roll shape).

[0044] It should be noted that the reinforcing film can be in roll form, in single sheet form, or in form that has been cut or punched into appropriate shapes according to its application and usage. The adhesive layer in the disclosed technology is typically formed continuously, but is not limited to this; for example, it can also be formed into regular or random patterns such as dots or stripes.

[0045] <Adhesive layer>

[0046] The reinforcing film disclosed herein includes an adhesive layer comprising polymer (A) and polymer (B). Such an adhesive layer can be formed from an adhesive composition containing polymer (A) and polymer (B), which are either entirely or partially polymers of monomeric raw material A. The form of the adhesive composition is not particularly limited, and can be various forms such as solvent-based, water-dispersible, hot-melt, or photocurable (e.g., photocurable).

[0047] (Polymer(A))

[0048] Acrylic polymers are preferably used as polymer (A) in the aforementioned adhesive layer. Using an acrylic polymer as polymer (A) tends to easily achieve good compatibility with polymer (B). Good compatibility between polymer (A) and polymer (B) can help reduce initial adhesive strength and increase adhesive strength after heating by improving the mobility of polymer (B) within the adhesive layer, thus being preferred. Furthermore, acrylic polymers with high molecular design freedom are preferred as adhesive materials that can effectively improve both adhesive properties and flexibility. This is achieved by limiting the amount of nitrogen-containing monomers to a specified level and by setting the ratio (W...)... N / W Zr The desired effect is effectively achieved by using acrylic polymers as the composition of polymer (A).

[0049] In the reinforcing membrane disclosed herein, the polymer (A) is typically a major component of the polymer composition contained in the adhesive layer, i.e., a component comprising more than 50% by weight. For example, it can be a component comprising more than 75% by weight, more than 85% by weight, more than 90% by weight, or more than 95% by weight (e.g., more than 97% by weight) of the aforementioned polymer composition. In some embodiments, the polymer (A) can be a component comprising, for example, more than 50% by weight of the entire adhesive layer, or a component comprising more than 70% by weight, more than 80% by weight, more than 90% by weight, or more than 95% by weight (e.g., more than 97% by weight).

[0050] The polymer (A) contains at least monomer units derived from nitrogen-containing monomers, typically including monomer units derived from nitrogen-containing monomers and monomer units derived from alkyl (meth)acrylates.

[0051] For example, polymer (A) may be a polymer in which 50 or more of the monomer units derived from alkyl methacrylates are contained in 100 parts by weight of polymer (A), i.e., a polymer in which 50 or more of the total monomer components (monomer raw material A) used to prepare polymer (A) are alkyl methacrylates. As alkyl methacrylates, it is preferable to use those having 1 to 20 carbon atoms (i.e., C... 1-20 Alkyl (meth)acrylates with straight or branched alkyl groups. Considering the ease of obtaining a balance of properties, monomer raw material A contains (meth)acrylate C. 1-20 The proportion of alkyl esters can be, for example, 50% by weight or more, or 60% by weight or more. In some preferred embodiments, the monomer raw material A contains (meth)acrylic acid C. 1-20 The proportion of alkyl ester is 70% by weight or more, more preferably 80% by weight or more, and even more preferably 85% by weight or more. By using the polymer (A) composed of this monomer, an adhesive that achieves a good balance between increased adhesive strength and flexibility can be readily obtained. Furthermore, from the viewpoint of easily obtaining the effects brought about by using a nitrogen-containing monomer, the (meth)acrylic acid C in monomer raw material A... 1-20 The proportion of alkyl esters is appropriately 99.9% by weight or less, or 99.8% by weight or less, or even 99.5% by weight or less. In some formulations, the monomer raw material A contains (meth)acrylic acid C. 1-20 The proportion of alkyl esters can be, for example, 98% by weight or less, 95% by weight or less, or 92% by weight or less.

[0052] As (meth)acrylic acid C 1-20Non-limiting specific examples of alkyl esters include: methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and so on. Nonyl acrylate, isononyl acrylate, decyl acrylate, isodecyl acrylate, undecyl acrylate, dodecyl acrylate, tridecyl acrylate, tetradecyl acrylate, pentadecyl acrylate, hexadecyl acrylate, heptadecanyl acrylate, stearyl acrylate, isostearyl acrylate, nonadecanyl acrylate, eicosyl acrylate, etc.

[0053] Among these, it is preferred to use at least (meth)acrylic acid C. 1-18 Alkyl esters, more preferably using at least (meth)acrylic acid C 1-14 Alkyl esters. In some formulations, the acrylic polymer may contain C(meth)acrylate. 4-12 Alkyl ester (preferably C14 acrylic acid) 4-10 Alkyl esters, such as C14 acrylic acid 6-10 At least one of alkyl esters is used as a monomer unit. For example, acrylic polymers containing one or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) are preferred, and acrylic polymers containing at least 2EHA are particularly preferred.

[0054] In some preferred embodiments, acrylic acid C in monomer raw material A used to prepare polymer (A) 6-10 Alkyl ester (preferably C14 acrylic acid) 8-9 The proportion of alkyl esters (typically 2EHA) is 70% by weight or more, more preferably 80% by weight or more, and even more preferably 85% by weight or more. The acrylic polymer composed of this monomer particularly preferably achieves the effects brought about by the technology disclosed herein. Furthermore, the acrylic acid C in monomer raw material A... 6-10 Alkyl ester (preferably C14 acrylic acid) 8-9 The proportion of alkyl esters (typically 2EHA) can be, for example, 99.9% by weight or less, 99.5% by weight or less, or 99% by weight or less. From the viewpoint of initial light peelability, it can be 98% by weight or less, or 95% by weight or less, or 92% by weight or less.

[0055] The monomer component (monomer raw material A) used to prepare polymer (A) includes nitrogen-containing monomers, i.e., monomers containing nitrogen atoms. By appropriately using nitrogen-containing monomers, the cohesiveness and polarity of the adhesive can be adjusted, and the adhesive strength after the increase in adhesive strength can be improved (e.g., the adhesive strength to polyimide films). Nitrogen-containing monomers can be used alone or in appropriate combinations of two or more.

[0056] The following monomers can be listed as non-limiting examples of nitrogen-containing monomers.

[0057] Monomers containing a nitrogen-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrrazine, N-vinylpyrrole, N-vinylimidazolium, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylmorpholine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinidone, N-vinylpyrazole, N-vinylisoxazole, N-vinyl... Alkenylthiazoles, N-vinylisothiazoles, N-vinylpyridazines, etc.; monomers with a succinimide skeleton, such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, N-(meth)acryloyl-8-oxyhexamethylenesuccinimide; maleimides such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide; and itaconimides such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, N-laurylitaconimide.

[0058] Monomers containing amide groups: for example, (meth)acrylamide; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di-n-butyl (meth)acrylamide, N,N-di-tert-butyl (meth)acrylamide, etc.; N,N-dialkyl (meth)acrylamide; N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-n-butyl (meth)acrylamide, etc.; N-alkyl (meth)acrylamides; N-vinylacetamide, etc.; N-vinylcarboxylic acid amides; monomers having hydroxyl and amide groups, such as N-(2... N-hydroxyalkyl (methyl)acrylamides, such as N-(2-hydroxypropyl) (methyl)acrylamide, N-(1-hydroxypropyl) (methyl)acrylamide, N-(3-hydroxypropyl) (methyl)acrylamide, N-(2-hydroxybutyl) (methyl)acrylamide, N-(3-hydroxybutyl) (methyl)acrylamide, N-(4-hydroxybutyl) (methyl)acrylamide, etc.; monomers having alkoxy and amide groups, such as N-alkoxyalkyl (methyl)acrylamide, N-methoxyethyl (methyl)acrylamide, N-butoxymethyl (methyl)acrylamide, etc.; and N,N-dimethylaminopropyl (methyl)acrylamide, etc.

[0059] (Meth)acrylate aminoalkyl esters: for example, (meth)acrylate aminoethyl ester, (meth)acrylate N,N-dimethylaminoethyl ester, (meth)acrylate N,N-diethylaminoethyl ester, (meth)acrylate tert-butylaminoethyl ester.

[0060] Monomers containing cyano groups: such as acrylonitrile, methacrylonitrile, etc.

[0061] Monomers containing isocyanate groups: for example, ethyl 2-isocyanate of (meth)acrylate.

[0062] In some schemes, from the viewpoint of ease of synthesis of polymer (A) and copolymerization with other monomer components (e.g., alkyl methacrylates), nitrogen-containing monomers having N-vinyl or N-(meth)acryloyl groups (e.g., one or more selected from the group consisting of monomers having a ring with a nitrogen atom, monomers containing amide groups, and aminoalkyl methacrylates) are preferred as nitrogen-containing monomers.

[0063] The amount of nitrogen-containing monomer used is the amount W of nitrogen-containing monomer contained in 100 parts by weight of polymer (A). N The amount is less than 14 parts by weight, meaning that the nitrogen-containing monomer in the total amount of the monomer component (monomer raw material A) used to prepare the polymer (A) is less than 14% by weight. By using W NLimiting the content to 14 parts by weight or less can improve the flexibility of the adhesive in the low-temperature region (e.g., reduce the storage modulus at -20°C), achieving flexibility suitable for repeated bending and flexing. From the perspective of improving flexibility, in some formulations, the content of nitrogen-containing monomers in monomer raw material A is appropriately 12% by weight or less (i.e., W... N The amount used is typically 12 parts by weight or less, preferably 10% by weight or less, more preferably 8.0% by weight or less, and even more preferably 5.0% by weight or less, or 4.0% by weight or less, 3.0% by weight or less, or 2.0% by weight or less. Furthermore, the amount of nitrogen-containing monomer used is usually appropriately set to 0.01% by weight or more of monomer raw material A (preferably 0.1% by weight or more, for example, 0.3% by weight or more). From the viewpoint of easily obtaining higher performance, in some embodiments, the amount of nitrogen-containing monomer used can be set to 0.5% by weight or more of monomer raw material A (i.e., W... N (It can be 0.5 parts by weight or more), or it can be set to 0.7% by weight or more, 1.0% by weight or more, 1.2% by weight or more, or 1.5% by weight or more.

[0064] In some embodiments, monomer raw material A may include a monomer having a nitrogen-containing ring as the aforementioned nitrogen-containing monomer. By using a monomer having a nitrogen-containing ring as at least a portion of the nitrogen-containing monomer, there is a tendency to improve the compatibility between the polymer (A) formed from the aforementioned monomer raw material A and the aforementioned polymer (B). As a result, it is easy to obtain a reinforcing film with improved adhesion and high adhesion after the adhesion has increased (e.g., adhesion to polyimide films).

[0065] Monomers having a nitrogen-containing ring, for example, appropriately selected from the examples above, can be used alone or in combination of two or more. In some embodiments, monomer raw material A preferably contains at least one monomer selected from the group consisting of N-vinyl cyclic amides and cyclic amides having (meth)acryloyl groups as a monomer having a nitrogen-containing ring.

[0066] Specific examples of N-vinylcyclic amides include: N-vinyl-2-pyrrolidone, N-vinyl-2-piperidinone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione. Preferred examples are N-vinyl-2-pyrrolidone (NVP) and N-vinyl-2-caprolactam.

[0067] Specific examples of cyclic amides having a (meth)acrylyl group include: N-(meth)acryl-2-pyrrolidone, N-(meth)acryloperidine, N-(meth)acrylpyrrolidine, N-(meth)acrylmorpholine, etc. As a preferred example, N-acrylmorpholine (ACMO) is mentioned.

[0068] There is no particular limitation on the amount of monomers with nitrogen-containing rings used, as long as W is the amount of monomer units derived from monomers with nitrogen-containing rings contained in 100 parts by weight of polymer (A). RN [Parts by weight] Not exceeding the amount W of the nitrogen-containing monomers mentioned above. N The range of [parts by weight] is acceptable. In other words, the amount [by weight %] of monomers with nitrogen-containing rings in the total amount of monomer raw material A can be appropriately set within the range not exceeding the amount [by weight %] of the aforementioned nitrogen-containing monomers in the total amount of monomer raw material A. Therefore, the amount W of monomers with nitrogen-containing rings contained in 100 parts by weight of polymer (A) is... RN The amount of monomers containing nitrogen-containing rings in the total amount of monomer raw material A is 14 parts by weight or less. In some embodiments, the amount of monomers containing nitrogen-containing rings is appropriately 12% by weight or less of monomer raw material A (i.e., W). RN The amount used is typically 12 parts by weight or less, preferably 10% by weight or less, more preferably 8.0% by weight or less, and even more preferably 5.0% by weight or less. It can also be 4.0% by weight or less, 3.0% by weight or less, or 2.0% by weight or less. Furthermore, the amount of monomer having a nitrogen-containing ring is usually suitably set to 0.01% by weight or more of monomer raw material A (preferably 0.1% by weight or more, for example, 0.3% by weight or more). From the viewpoint of easily obtaining higher performance, it can be set to 0.5% by weight or more of monomer raw material A (i.e., W). RN (It can be 0.5 parts by weight or more), or it can be set to 0.7% by weight or more, 1.0% by weight or more, 1.2% by weight or more, or 1.5% by weight or more.

[0069] In embodiments using monomers with nitrogen-containing rings, the proportion of monomers with nitrogen-containing rings in the nitrogen-containing monomer raw material A can be, for example, 30% by weight or more, preferably 50% by weight or more, more preferably 70% by weight or more, 85% by weight or more, 90% by weight or more, 95% by weight or more, or 100% by weight. In some embodiments, the amount of nitrogen-containing monomers in the total amount of monomer raw material A that is not equivalent to monomers with nitrogen-containing rings is, for example, 5% by weight or less, preferably 3% by weight or less, more preferably 1% by weight or less, 0.5% by weight or less, or 0.1% by weight or less. Alternatively, nitrogen-containing monomers that are not equivalent to monomers with nitrogen-containing rings may not be used. In addition, in some schemes, monomers with nitrogen-containing rings can be used in combination with other nitrogen-containing monomers. In such schemes, the proportion of monomers with nitrogen-containing rings in the nitrogen-containing monomers contained in monomer raw material A can be, for example, 98% by weight or less, or 93% by weight or less, 80% by weight or less, 60% by weight or less, or 40% by weight or less.

[0070] Monomer raw material A may also contain the aforementioned nitrogen-containing monomers, and typically further contain alkyl (meth)acrylates and, if necessary, other monomers (copolymeric monomers) that can copolymerize with alkyl (meth)acrylates. Monomers having polar groups (e.g., carboxyl, hydroxyl, etc.) are preferred as copolymeric monomers. Monomers with polar groups can help introduce crosslinking points into polymer (A) or improve the cohesiveness of polymer (A). One copolymeric monomer may be used alone or in combination of two or more.

[0071] The following monomers can be listed as non-limiting examples of copolymerizable monomers.

[0072] Hydroxyl-containing monomers: such as 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate, 8-hydroxyoctyl methacrylate, 10-hydroxydecyl methacrylate, 12-hydroxylaurate methacrylate, methyl methacrylate (4-hydroxymethylcyclohexyl) methacrylate, etc., and hydroxyalkyl methacrylates.

[0073] Monomers containing carboxyl groups: such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc.

[0074] Monomers containing anhydride groups: such as maleic anhydride and itaconic anhydride.

[0075] Monomers containing sulfonic acid or phosphoric acid groups: such as styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamide propanesulfonic acid, (meth)acrylate propyl sulfonate, (meth)acryloyloxynaphthalene sulfonic acid, 2-hydroxyethylacryloyl phosphate, etc.

[0076] Monomers containing epoxy groups: such as glycidyl (meth)acrylate, 2-ethyl glycidyl (meth)acrylate, and other epoxy-containing acrylates, allyl glycidyl ether, and glycidyl (meth)acrylate.

[0077] Alkoxy-containing monomers: such as 2-methoxyethyl acrylate, 3-methoxypropyl acrylate, 2-ethoxyethyl acrylate, propoxyethyl acrylate, butoxyethyl acrylate, ethoxypropyl acrylate, etc. (meth)acrylate alkoxyalkyl esters; methoxyethylene glycol acrylate, methoxypolypropylene glycol acrylate, etc. (meth)acrylate alkoxyalkylene glycol esters.

[0078] (Meth)acrylates with alicyclic hydrocarbon groups: for example, cyclopentyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, dicyclopentyl methacrylate, etc.

[0079] (Meth)acrylates containing aromatic hydrocarbon groups: for example, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, etc.

[0080] Vinyl ethers: such as methyl vinyl ether, ethyl vinyl ether, and other vinyl alkyl ethers.

[0081] Ethylene esters: such as vinyl acetate, vinyl propionate, etc.

[0082] Aromatic vinyl compounds: such as styrene, α-methylstyrene, vinyltoluene, etc.

[0083] Olefins: such as ethylene, butadiene, isoprene, isobutene, etc.

[0084] In addition, heterocyclic (meth)acrylates such as tetrahydrofurfuryl (meth)acrylate, halogenated (meth)acrylates such as (meth)acrylates containing vinyl chloride or fluorine atoms, silicon-containing (meth)acrylates such as organosilicon (meth)acrylates, and (meth)acrylates obtained from terpene compound derivative alcohols, etc.

[0085] When using such a copolymerizable monomer, its usage is not particularly limited, and is usually appropriately set to 0.01% by weight or more of monomer raw material A. From the viewpoint of better utilizing the effects brought about by the use of the copolymerizable monomer (e.g., the effect of improved cohesiveness), the usage of the copolymerizable monomer can be set to 0.1% by weight or more of monomer raw material A, or 0.5% by weight or more. In some embodiments, the content of the copolymerizable monomer in monomer raw material A is preferably 0.7% by weight or more, more preferably 1% by weight or more, and can be 3% by weight or more, 5% by weight or more, or 7% by weight or more (e.g., 8% by weight or more). Furthermore, the usage of the copolymerizable monomer can be, for example, 50% by weight or less of monomer raw material A, appropriately 30% by weight or less, preferably 20% by weight or less, more preferably 15% by weight or less (e.g., 12% by weight or less), 10% by weight or less, or 8% by weight or less, 6% by weight or less, 4% by weight or less, or 2% by weight or less. Limiting the amount of comonomers used can be advantageous from the perspective of improving the flexibility of the adhesive (especially in low-temperature regions).

[0086] In some preferred embodiments, monomer raw material A comprises a hydroxyl-containing monomer. By using the hydroxyl-containing monomer, the cohesiveness and polarity of the adhesive can be adjusted, preferably achieving the effects brought about by the technology disclosed herein. Furthermore, the hydroxyl-containing monomer provides reaction sites with crosslinking agents (e.g., isocyanate-based crosslinking agents) described later, thereby improving the cohesiveness of the adhesive through crosslinking reactions.

[0087] As hydroxyl-containing monomers, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and N-(2-hydroxyethyl)(meth)acrylamide are preferred. Among these, 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA) are preferred examples. From the viewpoint of suppressing the reduction of adhesive flexibility and improving cohesiveness, 4HBA is particularly preferred.

[0088] There is no particular limitation on the amount of hydroxyl-containing monomer used, but it is generally appropriate to set it to 40% by weight or less of monomer raw material A, and it can be set to 30% by weight or less, or even 20% by weight or less. In some embodiments, from the viewpoint of the flexibility of the adhesive (especially the flexibility in low-temperature regions), the content of hydroxyl-containing monomer in monomer raw material A is preferably 15% by weight or less (e.g., less than 15% by weight), more preferably 12% by weight or less, and can be 10% by weight or less, or even 8% by weight or less, 6% by weight or less, 4% by weight or less, or 2% by weight or less. By limiting the amount of hydroxyl-containing monomer used, the mobility of polymer (B) in the adhesive layer is improved, and it is easier to achieve an increase in adhesive strength. In addition, the amount of hydroxyl-containing monomer used is appropriately set to 0.01% by weight or more of monomer raw material A (preferably 0.1% by weight or more, for example, 0.5% by weight or more). From the viewpoint of obtaining adequate cohesion, in some schemes, the amount of hydroxyl-containing monomer used is preferably 0.7% by weight or more of monomer raw material A, more preferably 1% by weight or more, and can be 3% by weight or more, 5% by weight or more, or 7% by weight or more (for example, 8% by weight or more).

[0089] In some embodiments, a nitrogen-containing monomer (e.g., a monomer having a ring containing nitrogen atoms) and a hydroxyl-containing monomer can be used together as comonomers. In this case, the total amount of the nitrogen-containing monomer and the hydroxyl-containing monomer can be, for example, 0.1% by weight or more of monomer raw material A, preferably 1% by weight or more, more preferably 3% by weight or more, further preferably 5% by weight or more, particularly preferably 7% by weight or more (e.g., 9% by weight or more), can be 10% by weight or more, can be 15% by weight or more, can be 20% by weight or more, or can be 25% by weight or more. Furthermore, the total amount of the nitrogen-containing monomer and the hydroxyl-containing monomer can be, for example, 50% by weight or less of monomer raw material A, preferably 30% by weight or less. In some preferred embodiments, the total amount of the nitrogen-containing monomer and the hydroxyl-containing monomer is 20% by weight or less of monomer raw material A, more preferably 15% by weight or less (e.g., 12% by weight or less).

[0090] In a scheme where monomer feedstock A comprises a nitrogen-containing monomer (e.g., a monomer having a ring containing nitrogen atoms) and a hydroxyl-containing monomer, the content (W) of the nitrogen-containing monomer in monomer feedstock A is... N ) and the content of hydroxyl-containing monomers (W OH The relationship between W and (weight standard) is not specifically defined. N / W OH For example, it can be above 0.01, usually above 0.05, above 0.10, or above 0.12. Furthermore, W N / W OH For example, it can be less than 10, usually less than 1, preferably less than 0.50, less than 0.30, less than 0.20, or less than 0.15.

[0091] In some embodiments, monomer raw material A preferably does not contain monomers (monomer S1) having a polyorganosiloxane backbone, which are preferably used as components of monomer raw material B described later, or the content of such monomers is less than 10% by weight of monomer raw material A (more preferably less than 5% by weight, for example less than 2% by weight). With monomer raw material A having such a composition, it is preferable to achieve a reinforced film that appropriately balances initial reprocessing and strong adhesion after the adhesion has increased. For the same reason, in other embodiments, monomer raw material A preferably does not contain monomer S1, or if it does contain monomer S1, its content (by weight) is lower than the content of monomer S1 in monomer raw material B.

[0092] Glass transition temperature T of polymer (A) A There are no particular limitations; the preferred characteristics can be obtained from the reinforcing membrane disclosed herein. In some embodiments, T is preferred. AA polymer (A) with a temperature below 0°C. Adhesives containing such a polymer (A) exhibit moderate fluidity (e.g., the mobility of the polymer chains contained in the adhesive), and are therefore suitable for producing reinforcing films whose adhesive strength increases to above a specified value upon heating. The reinforcing films disclosed herein can be used with T... A Polymer (A) with a temperature range of less than -10°C, less than -20°C, less than -30°C, or less than -35°C is preferred. In some embodiments, T A It can be below -40℃ or below -45℃. In some designs, considering the need to improve flexibility in low-temperature regions, T... A Preferably below -50°C, more preferably below -55°C, even more preferably below -58°C, but can be below -60°C, below -62°C, or below -65°C. A There is no particular limitation on the lower limit. Considering the ease of material availability and improving the cohesiveness of the adhesive layer, T is generally preferred. A Polymers with temperatures above -80°C, -75°C, or -70°C (A). In some schemes, T A For example, it can be above -65℃ or above -63℃.

[0093] In this specification, the glass transition temperature (Tg) of a polymer refers to the nominal value recorded in literature, catalogs, etc., or the Tg calculated according to the Fox formula based on the composition of the monomer raw materials used to prepare the polymer. The Fox formula, shown below, is a relationship between the Tg of the copolymer and the glass transition temperature Tgi of the homopolymer formed by homopolymerizing each of the monomers constituting the copolymer.

[0094] 1 / Tg=Σ(Wi / Tgi)

[0095] In the above Fox formula, Tg represents the glass transition temperature of the copolymer (in K), Wi represents the weight fraction of monomer i in the copolymer (weight-based copolymerization ratio), and Tgi represents the glass transition temperature of the homopolymer of monomer i (in K). When the target polymer for determining Tg is a homopolymer, the Tg of the homopolymer is consistent with the Tg of the target polymer.

[0096] The glass transition temperature (Tg) of the homopolymer used for calculating Tg is the value recorded in known sources. Specifically, the values ​​are listed in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989). For monomers for which multiple values ​​are recorded in the aforementioned Polymer Handbook, the highest value is used.

[0097] The glass transition temperature of homopolymers of monomers not described in the aforementioned polymer handbook is the value obtained by the following determination method.

[0098] Specifically, 100 parts by weight of monomer, 0.2 parts by weight of 2,2'-azobisisobutyronitrile, and 200 parts by weight of ethyl acetate as the polymerization solvent were added to a reactor equipped with a thermometer, stirrer, nitrogen inlet pipe, and reflux condenser. The mixture was stirred for 1 hour while nitrogen was flowing through it. After removing oxygen from the polymerization system, the temperature was raised to 63°C, and the reaction was allowed to proceed for 10 hours. Then, the mixture was cooled to room temperature to obtain a homopolymer solution with a solid content of 33% by weight. This homopolymer solution was then cast onto a release liner, dried, and used to prepare test samples (sheet-like homopolymer) approximately 2 mm thick. The test sample was punched into a disc shape with a diameter of 7.9 mm, clamped with parallel plates, and viscoelasticity was measured in shear mode using a viscoelasticity testing machine (manufactured by TA Instruments Japan, model name "DHR-2") while a shear strain of 1 Hz was applied, and the temperature range of -70℃ to 150℃ was increased at a rate of 5℃ / min. The temperature corresponding to the peak temperature of tanδ was set as the Tg of the homopolymer.

[0099] The weight-average molecular weight (Mw) of polymer (A) is typically suitably about 20 × 10⁻⁶. 4 The above is not particularly limited. Based on the polymer (A) with this Mw, adhesives exhibiting good cohesiveness can be readily obtained. From the viewpoint of obtaining even higher cohesiveness, in some preferred embodiments, the Mw of polymer (A) can, for example, be 30 × 10⁻⁶. 4 The above can also be 40×10 4 The above can also be 50×10 4 The above can also be 60×10 4 The above can also be 80×10 4 That's all. Furthermore, the Mw of polymer (A) is typically suitably about 500 × 10⁻⁶. 4 The polymer (A) with the specified Mw readily forms an adhesive exhibiting moderate flowability (mobility of the polymer chains), thus making it suitable for achieving reinforcing films with low initial adhesive strength and high initial adhesive strength. It is also preferable that the Mw of polymer (A) is not too high from the viewpoint of improving compatibility with polymer (B). In some preferred embodiments, the Mw of polymer (A) can be, for example, 250 × 10⁻⁶. 4 The following can also be 200×10 4 The following can also be 150×10 4 The following can also be 100×10 4 The following can also be 70×10 4 the following.

[0100] It should be noted that, in this specification, the Mw of polymer (A) and polymer (B) described later can be determined by polystyrene conversion using gel permeation chromatography (GPC). More specifically, Mw can be determined according to the methods and conditions described in the examples described later.

[0101] There are no particular limitations on the method for obtaining polymer (A). Various polymerization methods can be appropriately employed, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization. In some schemes, solution polymerization is preferred. The polymerization temperature during solution polymerization can be appropriately selected based on the types of monomers and solvents used, as well as the type of polymerization initiator. For example, it can be set to approximately 20℃ to 170℃ (typically 40℃ to 140℃).

[0102] The initiator used for polymerization can be appropriately selected from conventionally known thermal polymerization initiators, photopolymerization initiators, etc., depending on the polymerization method. A single polymerization initiator can be used alone, or two or more can be used in combination.

[0103] Examples of thermal polymerization initiators include: azo-based polymerization initiators (e.g., 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionic acid)dimethyl ester, 4,4'-azobis-4-cyanopentanoic acid, azobisisovalerate, 2,2'-azobis(2-amidinylpropane)dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropanedisulfate), 2,2'-azobis(N,N'-dimethyleneisobutylamidine)dihydrochloride, etc.); persulfates such as potassium persulfate; peroxide-based polymerization initiators (e.g., benzoyl peroxide, tert-butyl maleate peroxide, lauroyl peroxide, etc.); and redox-based polymerization initiators, etc. There is no particular limitation on the amount of thermal polymerization initiator used. For example, it can be set to 0.01 to 5 parts by weight, preferably 0.05 to 3 parts by weight, relative to 100 parts by weight of the monomer component (monomer raw material A) used in the preparation of the acrylic polymer.

[0104] There are no particular limitations on the photopolymerization initiator used. For example, benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-keto alcohol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzoyl-based photopolymerization initiators, ketal-based photopolymerization initiators, thioxanone-based photopolymerization initiators, and acylphosphine oxide-based photopolymerization initiators can be used. There are no particular limitations on the amount of photopolymerization initiator used; for example, it can be set to 0.01 parts by weight to 5 parts by weight relative to the monomer raw material A100, preferably in the range of 0.05 parts by weight to 3 parts by weight.

[0105] In some embodiments, polymer (A) can be included in the adhesive composition for forming the adhesive layer in the form of a partial polymer (polymer slurry) obtained by irradiating a mixture of monomer raw material A, which is formulated with a polymerization initiator as described above, with ultraviolet light (UV) to polymerize a portion of the monomer component. The adhesive composition containing the polymer slurry can be applied to a specified substrate, and the polymerization can be completed by irradiating with UV light. That is, the polymer slurry can be understood as a precursor of polymer (A). The adhesive layer disclosed herein can be formed, for example, using an adhesive composition containing the polymer slurry and polymer (B).

[0106] (Polymer(B))

[0107] The polymer (B) disclosed herein is a polymer comprising a monomer component (monomer raw material B) having a polysiloxane backbone (hereinafter also referred to as "monomer S1") and a (meth)acrylic monomer. Polymer (B) may be referred to as a copolymer of monomer S1 and (meth)acrylic monomer. Polymer (B) may be used alone or in combination of two or more. Polymer (B), due to the low polarity and mobility of the polysiloxane structure derived from monomer S1, functions as an adhesive force retarder, suppressing initial adhesive force upon bonding to the substrate and increasing adhesive force upon heating. As monomer S1, there is no particular limitation; any monomer containing a polysiloxane backbone may be used. Due to the low polarity derived from its structure, monomer S1 promotes the tendency of polymer (B) to be present on the surface of the adhesive layer in the reinforcing film before use (before bonding to the substrate), exhibiting mild peeling (low adhesion) in the initial bonding stage. As monomer S1, a monomer with a structure having a polymerizable reactive group at a single end is preferably used. Based on a composition comprising monomer S1 units and (meth)acrylic acid monomer units, a polymer (B) with a polyorganosiloxane backbone in its side chains is formed. This polymer (B) readily exhibits low initial adhesion and high adhesion upon heating due to the mobility and ease of movement of its side chains. Furthermore, in some embodiments, monomer S1 is preferably a monomer having a polymerizable reactive group at one end and no functional group at the other end that would crosslink with polymer (A). Polymer (B) copolymerized from monomer S1 with such a structure readily exhibits low initial adhesion and high adhesion upon heating due to the mobility of the polyorganosiloxane structure derived from monomer S1.

[0108] As monomer S1, compounds represented by the following general formula (1) or (2) can be used, for example. More specifically, examples of single-terminal reactive silicone oils manufactured by Shin-Etsu Chemical Co., Ltd. include: X-22-174ASX, X-22-2426, X-22-2475, KF-2012, etc. Monomer S1 can be used alone or in combination of two or more.

[0109]

[0110] Here, R in the above general formulas (1) and (2) 3 For hydrogen or methyl, R 4 It is a methyl or monovalent organic group, and m and n are integers greater than or equal to 0.

[0111] The functional group equivalent of monomer S1 can be an appropriate value within the range that allows the desired effect to be achieved using monomer S1, and is not limited to a specific range. From the viewpoint of sufficiently suppressing initial adhesive force, the aforementioned functional group equivalent is, for example, 100 g / mol or more, or 200 g / mol or more, appropriately 300 g / mol or more (e.g., 500 g / mol or more), preferably 800 g / mol or more, and more preferably 1500 g / mol or more. In a particularly preferred embodiment, from the viewpoint of balancing low initial adhesion and increased adhesive force after heating, the aforementioned functional group equivalent is appropriately 2000 g / mol or more, for example, 2500 g / mol or more, 3000 g / mol or more, 4000 g / mol or more, or 5000 g / mol or more. In other embodiments, the aforementioned functional group equivalent is, for example, 9000 g / mol or more, 12000 g / mol or more, or 15000 g / mol or more.

[0112] From the viewpoint of maximizing adhesive strength, the aforementioned functional group equivalent is, for example, appropriately 30,000 g / mol or less, but can be 20,000 g / mol or less, less than 15,000 g / mol, or less than 10,000 g / mol. In some preferred embodiments, the functional group equivalent of monomer S1 is 7,000 g / mol or less, more preferably 5,500 g / mol or less, even more preferably 5,000 g / mol or less, but can be 4,500 g / mol or less, 4,200 g / mol or less, 4,000 g / mol or less, or 3,500 g / mol or less, or 3,200 g / mol or less. If the functional group equivalent of monomer S1 is within the above range, the compatibility within the adhesive layer (e.g., compatibility with polymer (A)) can easily become good. In addition, the polyorganosiloxane backbone (chain) of polymer (B) has good mobility, and the mobility of polymer (B) can be easily adjusted to a suitable range, making it easy to achieve an adhesive layer that balances low initial adhesion and increased adhesion after heating.

[0113] Here, "functional group equivalent" refers to the weight of the backbone (e.g., polydimethylsiloxane) bonded to each functional group. The unit g / mol is used to convert to 1 mol of functional groups. The functional group equivalent of monomer S1 can be determined, for example, based on nuclear magnetic resonance (NMR)... 1 The spectral intensity was calculated from H-NMR (proton NMR). Based on 1 The calculation of the functional group equivalent (g / mol) of monomer S1 based on the spectral intensity of H-NMR can be based on 1The usual structural analysis method for H-NMR spectroscopy is performed as described in Japanese Patent No. 5951153, as needed. In the functional group equivalent of monomer S1, the aforementioned functional groups refer to polymerizable functional groups (e.g., (meth)acryloyl, vinyl, allyl, and other olefinic unsaturated groups).

[0114] It should be noted that when using two or more monomers with different functional group equivalents as monomer S1, the functional group equivalent of monomer S1 can be the arithmetic mean. That is, when n monomers with different functional group equivalents (monomer S11, monomer S12...monomer S1 ... n The functional group equivalent of monomer S1 can be calculated using the following formula.

[0115] Functional group equivalent of monomer S1 (g / mol) = (functional group equivalent of monomer S11 × coordination amount of monomer S11 + functional group equivalent of monomer S12 × coordination amount of monomer S12 + ... + monomer S1) n Functional group equivalent × monomer S1 n (Amount of monomer S11) / (Amount of monomer S12 + Amount of monomer S11 + ... + Amount of monomer S1) n (the amount of mixture)

[0116] The content of monomer S1 can be appropriately selected within the range where the desired effect is achieved using monomer S1, and is not limited to a specific range. From the viewpoint of sufficiently suppressing initial adhesion, in some embodiments, the content of monomer S1 in the total amount of monomer components (monomer raw material B) used to prepare polymer (B) can be, for example, 5% by weight or more. From the viewpoint of better exerting its effect as a delayer for the increase in adhesion, it is preferably set to 10% by weight or more, more preferably 12% by weight or more, further preferably 15% by weight or more, particularly preferably 18% by weight or more, and may also be set to 20% by weight or more. Furthermore, from the viewpoint of polymerization reactivity and compatibility, the content of monomer S1 in monomer raw material B can be, for example, 80% by weight or less, appropriately set to 60% by weight or less, preferably 50% by weight or less, more preferably 40% by weight or less, and further preferably 30% by weight or less. By setting the polymerization ratio of monomer S1 within an appropriate range, an appropriate increase in adhesion can be achieved.

[0117] Monomer raw material B contains monomer S1, as well as (meth)acrylic monomers that can copolymerize with monomer S1. By using one or more (meth)acrylic monomers, the mobility of polymer (B) within the adhesive layer can be appropriately adjusted. Furthermore, it also helps improve the compatibility between polymer (B) and polymer (A). Polymer (B) containing (meth)acrylic monomer units is well compatible with polymer (A) (an acrylic polymer), thus it is easy to reduce initial adhesive strength and increase adhesive strength after heating by improving the mobility of polymer (B) within the adhesive layer.

[0118] In the polymer (B) used in the disclosed technology, the composition of the (meth)acrylic acid monomer contained in the monomer raw material B is preferably set to a glass transition temperature T based on the composition of the (meth)acrylic acid monomer. B1 Higher than the glass transition temperature T of polymer (A) A T B1 For example, it can be set to above 0°C. Here, the glass transition temperature T is based on the composition of the (meth)acrylic monomer. B1 Tg refers to the Tg calculated according to the Fox formula based on the composition of only (meth)acrylate monomers in the monomer components used to prepare polymer (B). B1 The glass transition temperature (T) can be calculated using the above-mentioned Fox formula, taking only (meth)acrylate monomers in the monomer composition used to prepare polymer (B) as the object, based on the glass transition temperature of the homopolymer of each (meth)acrylate monomer and the weight fraction of each (meth)acrylate monomer in the total amount of that (meth)acrylate monomer. The glass transition temperature T is used as the basis for this calculation. B1 Relatively high (typically above 0°C) polymers (B) tend to suppress initial adhesive strength. Furthermore, based on the glass transition temperature T... B1 Relatively high (typically above 0°C) polymers (B) readily yield reinforcing films with a high rate of increase in adhesive strength.

[0119] In some preferred solutions, T B1 The temperature is 10°C or higher, more preferably 30°C or higher, even more preferably 40°C or higher, and may also be 45°C or higher. If T B1 As the adhesion height increases, the initial adhesive force tends to be better suppressed. This is believed to be because, according to T... B1For polymer (B) at temperatures above a specified temperature, the increased mobility and fluidity of the polyorganosiloxane structural portion in the high-temperature region, where the temperature rises to room temperature or above a certain level, is effectively suppressed by the monomer units derived from (meth)acrylic acid monomers contained in polymer (B), thus better maintaining the low adhesion obtained due to the presence of the aforementioned polyorganosiloxane structural portion. From the viewpoint of better maintaining the low adhesion in the initial stage of bonding, in some solutions, T... B1 For example, it can be above 50℃, above 55℃, or above 60℃. Furthermore, T B1 For example, it can be below 120℃ or below 100℃. If T... B1 If the temperature decreases, there is a tendency for the adhesive strength to increase through heating, which facilitates adhesion. In some preferred embodiments, T... B1 For example, the temperature is below 90°C, more preferably below 70°C, even more preferably below 60°C, and particularly preferably below 55°C (for example, below 50°C).

[0120] From easy to play, T is appropriately set B1 From the perspective of the resulting effects, the total amount of monomer S1 and (meth)acrylic acid monomers in the total monomer composition used to prepare polymer (B) can be, for example, more than 50% by weight, more than 70% by weight, more than 85% by weight, more than 90% by weight, more than 95% by weight, or substantially more than 100% by weight.

[0121] Glass transition temperature T of polymer (B) B Without particular limitation, it can be selected in a manner that yields preferred properties in the reinforcing membrane disclosed herein. The T of polymer (B) B For example, it can be below 50°C, below 30°C, below 20°C, below 15°C, or below 10°C. If the T of polymer (B) B As the temperature decreases, the mobility (typically thermosensitive mobility) of the polymer (B) increases, leading to a significant increase in adhesive strength. In some preferred embodiments, the Tg of the polymer (B) is... B The temperature can be below 5°C, less than 0°C, below -5°C, or below -10°C. Furthermore, in some designs, the T of polymer (B)... B For example, it can be above -40°C or above -30°C. T exists. B The higher the Tg, the more the polymer (B) tends to be present on the surface side of the adhesive layer when bonded to the substrate, which helps to reduce initial adhesion and results in better initial peel performance. In some preferred embodiments, the Tg of polymer (B) is... B It can be above -20℃, or above -15℃. By using T...B Setting it to an appropriate range allows for optimal control of the initial peeling during bonding and the increase in adhesive strength after heating.

[0122] In some schemes, the composition of the monomer components used to prepare polymer (B) can be set as T. B1 Higher than T B That is, T B1 -T B Above 0°C. Based on this composition, it is easy to appropriately utilize the composition of the (meth)acrylic monomers contained in the above-mentioned monomer components to adjust the mobility of polymer (B). T B1 -T B For example, it can be around 40℃ to 100℃, or around 50℃ to 90℃. In some preferred solutions, T B1 -T B The temperature is 45°C or higher, more preferably 50°C or higher, and even more preferably 55°C or higher (e.g., 58°C or higher). Furthermore, from the viewpoint of appropriately demonstrating the effect of containing polymer (B), T B1 -T B Preferably, the temperature is below 80°C, more preferably below 70°C, and even more preferably below 65°C (e.g., below 62°C).

[0123] From the viewpoint of easily controlling the mobility of polymer (B) within the adhesive layer, in some schemes, the composition of the monomer components used to prepare polymer (B) can be set to be similar to the glass transition temperature T of polymer (A). A In terms of relationship, T B T A Temperatures above 20°C (T) B -T A The temperature is above 20°C. In some preferred solutions, T B -T A For example, the temperature is 30°C or higher, more preferably 40°C or higher, even more preferably 50°C or higher, and can be 60°C or higher, or 70°C or higher. Furthermore, from the viewpoint of increased adhesive strength, T... B -T A For example, the temperature can be below 130°C, below 120°C, preferably below 100°C, more preferably below 80°C, and even more preferably below 65°C. It can also be below 55°C or below 45°C.

[0124] As monomers that can be used as monomer raw material B, alkyl methacrylates are examples of monomers that can be used as monomer raw material B. Here, "alkyl" refers to a chain-like (including linear and branched) alkyl group, excluding alicyclic hydrocarbon groups described later. For example, one or more of the monomers exemplified above, which are alkyl methacrylates that can be used as polymer (A), can be used as constituents of monomer raw material B. In some embodiments, monomer raw material B may contain (meth)acrylate C. 4- 12-alkyl ester (preferably (meth)acrylic acid C) 4-10 Alkyl esters, such as (meth)acrylic acid C 6-10 At least one of alkyl esters. In other embodiments, monomer feedstock B may contain methacrylic acid C. 1-18 Alkyl ester (preferably C methacrylate) 1-14 Alkyl esters, such as C-methacrylic acid 1-10 At least one of alkyl esters. Monomer raw material B may contain one or more of, for example, selected from MMA, n-butyl methacrylate (BMA), and 2-ethylhexyl methacrylate (2EHMA) as (meth)acrylic monomers.

[0125] Other examples of the aforementioned (meth)acrylate monomers include (meth)acrylates having alicyclic hydrocarbon groups. For example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, and 1-adamantyl (meth)acrylate can be used. In some embodiments, monomer raw material B may contain at least one selected from dicyclopentyl methacrylate, isobornyl methacrylate, and cyclohexyl methacrylate as a (meth)acrylate monomer.

[0126] The content of the alkyl (meth)acrylate and the (meth)acrylate having alicyclic hydrocarbon groups in monomer raw material B can be, for example, 10% by weight or more and 95% by weight or less, 20% by weight or more and 95% by weight or less, 30% by weight or more and 90% by weight or less, 40% by weight or more and 90% by weight or less, or 50% by weight or more and 85% by weight or less. From the viewpoint of ease of increase in adhesive strength caused by heating, the use of alkyl (meth)acrylate becomes advantageous. In some embodiments, the content of (meth)acrylate having alicyclic hydrocarbon groups can be less than 50% by weight of monomer raw material B, less than 30% by weight, less than 15% by weight, less than 10% by weight, or less than 5% by weight. Alternatively, (meth)acrylate having alicyclic hydrocarbon groups may not be used.

[0127] In some preferred embodiments, the aforementioned (meth)acrylic acid monomers, which are components of monomer raw material B, may include monomer M2, whose homopolymer has a Tg of 50°C or higher. In polymer (B), by copolymerizing monomer S1 with monomer M2, the mobility and fluidity of the polyorganosiloxane structural portion accompanying temperature increases can be appropriately controlled, easily achieving a balance between initial light peeling properties (reprocessability) and increased adhesive strength after heating. In some embodiments, the Tg of the homopolymer of monomer M2 can be 60°C or higher, or 70°C or higher, or 80°C or higher, or 90°C or higher. Furthermore, there is no particular upper limit to the Tg of the homopolymer of monomer M2; from the viewpoint of ease of synthesis of polymer (B), it is generally appropriate to be below 200°C. In some embodiments, the Tg of the homopolymer of monomer M2 can be, for example, below 180°C, below 150°C, or below 120°C.

[0128] As monomer M2, for example, a monomer whose Tg of the homopolymer of the (meth)acrylic monomers exemplified above meets the requirements can be used. For example, one or more monomers selected from the group consisting of alkyl (meth)acrylates and (meth)acrylates having alicyclic hydrocarbon groups can be used. As an alkyl (meth)acrylate, an alkyl methacrylate with the number of carbon atoms in the alkyl group in the range of 1 to 4 is preferably used.

[0129] In embodiments where monomer raw material B includes monomer M2, the content of monomer M2 can be, for example, 5% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, or 30% by weight or more of monomer raw material B. In some embodiments, the content of monomer M2 can be 35% by weight or more, 40% by weight or more, 45% by weight or more, 50% by weight or more, or 55% by weight or more of monomer raw material B. Furthermore, the content of monomer M2 can be, for example, 90% by weight or less, typically appropriately 80% by weight or less, preferably 75% by weight or less, and can be 70% by weight or less, or 65% by weight or less. In some preferred embodiments, the content of monomer M2 is 60% by weight or less (for example, 50% by weight or less, typically 42% by weight or less). In polymer (B), by limiting the copolymerization ratio of monomer M2, which has a Tg of 50°C or higher, to a specified value or lower, an increase in adhesive strength after heating can be preferably achieved based on the mobility of polymer (B) near 50°C. From the same perspective, the content of monomer M2 in monomer raw material B can be 35% by weight or less, 25% by weight or less, or 15% by weight or less (e.g., 5% by weight or less).

[0130] The content of the aforementioned monomer M2 can preferably be applied, for example, to a scheme in which monomer M2 comprises one or more monomers selected from the group consisting of alkyl (meth)acrylates and (meth)acrylates having alicyclic hydrocarbon groups, or to a scheme in which monomer M2 comprises one or more monomers selected from alkyl (meth)acrylates (e.g., alkyl methacrylate). As a preferred example of this scheme, a scheme in which the aforementioned monomer M2 comprises MMA can be cited.

[0131] In some formulations, the aforementioned (meth)acrylic acid monomers may also include monomer M3, whose homopolymer Tg is less than 50°C (typically above -20°C and less than 50°C). By using monomer M3, it is easy to obtain a reinforced film that balances adhesion and cohesion well after the adhesive strength increases. From the viewpoint of easily achieving this effect, monomer M3 is preferably used in combination with monomer M2.

[0132] As monomer M3, for example, monomers whose Tg of homopolymers of (meth)acrylic monomers exemplified above meets the requirements can be used. For example, one or more monomers selected from the group consisting of alkyl (meth)acrylic esters can be used.

[0133] In embodiments where monomer raw material B comprises monomer M3, the content of monomer M3 may be, for example, 5% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, or 35% by weight or more of monomer raw material B. Furthermore, the content of monomer M3 is typically suitably set to 70% by weight or less of monomer raw material B, and may be 60% by weight or less, or 50% by weight or less. The aforementioned content of monomer M3 is preferably applied, for example, to embodiments where monomer M3 comprises one or more monomers selected from alkyl methacrylates (e.g., alkyl methacrylates).

[0134] In some of the reinforced film designs disclosed herein, the monomer raw material B preferably contains 30% by weight or less of the monomer with a Tg higher than 170°C in the homopolymer. Here, unless otherwise specified, "monomer content of X% by weight or less" in this specification refers to designs where the monomer content is 0% by weight, i.e., designs that substantially do not contain the monomer. Furthermore, "substantially do not contain" means, at least not intentionally, the aforementioned monomer. If the copolymerization ratio of monomers with a Tg higher than 170°C in the homopolymer becomes high, the mobility of polymer (B) may be insufficient, making it difficult to increase the adhesive strength by heating to a temperature range higher than 50°C.

[0135] In some embodiments, monomer raw material B preferably contains at least MMA as a (meth)acrylic acid monomer. Based on the polymer (B) copolymerized with MMA, it is easy to obtain a reinforcing film with high adhesion after heating. The proportion of MMA in the total amount of (meth)acrylic acid monomers contained in monomer raw material B can be, for example, 5% by weight or more, 10% by weight or more, 20% by weight or more, 30% by weight or more, or 40% by weight or more. Furthermore, the proportion of MMA in the total amount of monomer raw material B is generally suitably 95% by weight or less. In some preferred embodiments, from the viewpoint of increased adhesion after heating, the proportion of MMA in the total amount of monomer raw material B can be 75% by weight or less, 65% by weight or less, 60% by weight or less, or 55% by weight or less (e.g., 50% by weight or less).

[0136] Other examples of monomers that can be included together with monomer S1 as monomer units constituting polymer (B) include: monomers containing carboxyl groups, monomers containing acid anhydride groups, monomers containing hydroxyl groups, monomers containing epoxy groups, monomers containing cyano groups, monomers containing isocyanate groups, monomers containing amide groups, monomers having a ring containing a nitrogen atom (N-vinyl cyclic amides, cyclic amides having (meth)acryloyl groups, monomers having a succinimide skeleton, maleimides, itaconimides, etc.), aminoalkyl esters of (meth)acrylate, vinyl esters, vinyl ethers, olefins, (meth)acrylates having aromatic hydrocarbon groups, (meth)acrylates containing heterocyclic rings, (meth)acrylates containing halogen atoms, (meth)acrylates obtained from terpene compound derivative alcohols, etc.

[0137] Further examples of monomers that can be included together with monomer S1 as monomeric units constituting polymer (B) include: ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and other oxyalkylene di(meth)acrylates; monomers having a polyoxyalkylene backbone, such as those in polyethylene glycol, polypropylene glycol, etc. Polyoxyalkylene ethers, such as alcohols, have polymerizable functional groups such as (meth)acryloyl, vinyl, or allyl at one end and an ether structure (alkyl ether, aryl ether, arylalkyl ether, etc.) at the other end; methoxyethyl acrylate, ethoxyethyl acrylate, propoxyethyl acrylate, butoxyethyl acrylate, ethoxypropyl acrylate, and other alkoxyalkyl acrylates of (meth)acrylate; alkali metal salts of (meth)acrylate; trimethylolpropane tri(methyl) Poly(meth)acrylates such as acrylates; halogenated vinyl compounds such as vinylidene chloride and 2-chloroethyl(meth)acrylate; monomers containing oxazoline groups such as 2-vinyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, and 2-isopropenyl-2-oxazoline; monomers containing aziridinium groups such as aziridinium acrylate and 2-aziridinium ethyl(meth)acrylate; addition reactions of 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, lactones, and 2-hydroxyethyl(meth)acrylate. Vinyl monomers containing hydroxyl groups, such as hydroxyl groups; fluorinated vinyl monomers such as fluorinated alkyl (meth)acrylates; vinyl monomers containing reactive halogens such as 2-chloroethyl vinyl ether and vinyl monochloroacetate; vinyl monomers containing organosilicon such as vinyltrimethoxysilane, γ-(meth)acryloyloxypropyltrimethoxysilane, allyltrimethoxysilane, trimethoxysilylpropylallylamine, and 2-methoxyethoxytrimethoxysilane; and macromonomers of vinyl groups with free radical polymerizability at the ends of the monomers in which vinyl groups are polymerized. These can be copolymerized with monomer S1, either alone or in combination of two or more.

[0138] In some embodiments, polymer (B) is preferably a polymer that does not have functional groups that can crosslink with polymer (A). In other words, polymer (B) is preferably contained in the adhesive layer in a form that is not chemically bonded to polymer (A). An adhesive layer containing polymer (B) in this form exhibits good mobility of polymer (B) upon heating, which is suitable for increasing the rate of increase in adhesive strength. The functional groups that can crosslink with polymer (A) can vary depending on the type of functional groups possessed by polymer (A), and may be, for example, epoxy groups, isocyanate groups, carboxyl groups, alkoxysilyl groups, amino groups, etc.

[0139] The Mw of polymer (B) is not particularly limited. The Mw of polymer (B) can be, for example, 1000 or more, or 5000 or more. In some preferred embodiments, from the viewpoint of appropriately reflecting the increase in adhesive strength after heating, the Mw of polymer (B) is 10000 or more, more preferably 12000 or more, and can be 15000 or more, or 20000 or more, or 22000 or more, or 25000 or more. In other embodiments, the Mw of polymer (B) can be 30000 or more, or 50000 or more, or 70000 or more. The upper limit of the Mw of polymer (B) is, for example, 500000 or less, or 350000 or less, or 200000 or less, or 150000 or less. From the viewpoint of adjusting the compatibility and mobility within the adhesive layer to a suitable range, and appropriately reflecting low adhesion in the initial stage of bonding, in some preferred embodiments, the Mw of polymer (B) is 100,000 or less, more preferably 80,000 or less, even more preferably 60,000 or less, particularly preferably 40,000 or less (e.g., 30,000 or less), and can be 25,000 or less, and even more preferably 20,000 or less. By setting the Mw of polymer (B) to an appropriate range, it is easy to obtain an adhesive that balances light peeling and good adhesion growth in the initial stage of bonding.

[0140] In some preferred embodiments, the Mw of polymer (B) is preferably lower than that of polymer (A). This facilitates the creation of a reinforcing film that balances good reprocessability during the initial bonding phase with increased adhesive strength after heating. In some embodiments, the Mw of polymer (B) can be, for example, less than 0.8 times, less than 0.75 times, less than 0.5 times, or less than 0.3 times the Mw of polymer (A). In some preferred embodiments, the Mw of polymer (B)... B Mw relative to polymer (A) A The ratio (Mw) B / Mw A The content of (Mw) is 0.3 or less, more preferably 0.2 or less, further preferably 0.1 or less, and particularly preferably 0.06 or less (e.g., 0.05 or less). Furthermore, the ratio of (Mw) to... B / Mw A For example, it is appropriately 0.010 or more, preferably 0.020 or more, more preferably 0.03 or more, and even more preferably 0.04 or more. By setting the Mw of polymer (A) and polymer (B) to appropriate ranges, the effects brought about by the technology disclosed herein can be better achieved. In other embodiments, the Mw of polymer (B) may also be less than 0.03 times (e.g., less than 0.02 times) of the Mw of polymer (A).

[0141] Polymer (B) can be produced, for example, by polymerizing the aforementioned monomers using known methods such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization.

[0142] To adjust the molecular weight of polymer (B), chain transfer agents can be used as needed. Examples of chain transfer agents that can be used include: compounds with thiol groups such as octylthiol, laurylthiol, tert-nonylthiol, tert-dodecylthiol, mercaptoethanol, and α-thioglycerol; thioglycolic acid, methyl thioglycolate, ethyl thioglycolate, propyl thioglycolate, butyl thioglycolate, tert-butyl thioglycolate, 2-ethylhexyl thioglycolate, octyl thioglycolate, isooctyl thioglycolate, decyl thioglycolate, dodecyl thioglycolate, thioglycolates of ethylene glycol, neopentyl glycol, and pentaerythritol; and α-methylstyrene dimers. Chain transfer agents can be used alone or in combination of two or more.

[0143] There is no particular limitation on the amount of chain transfer agent used. Typically, it is 0.05 to 20 parts by weight relative to 100 parts by weight of the monomer, preferably 0.1 to 15 parts by weight, and more preferably 0.2 to 10 parts by weight. By adjusting the amount of chain transfer agent added in this way, a polymer (B) with an appropriate molecular weight can be obtained. In some preferred embodiments, the amount of chain transfer agent used is 5 parts by weight or less relative to 100 parts by weight of the monomer, more preferably 3 parts by weight or less, more preferably 2 parts by weight or less, and can be 1.5 parts by weight or less, or even 1 part by weight or less.

[0144] As a method for adjusting the molecular weight of polymer (B), various conventionally known methods, including the use of the aforementioned chain transfer agent, can be used alone or in appropriate combinations. The same applies to the molecular weight of polymer (A). Non-limiting examples of such methods include the selection of the polymerization method; the selection of the type and amount of the polymerization initiator; the selection of the polymerization temperature; the selection of the type and amount of the polymerization solvent in solution polymerization; and the selection of the light irradiation intensity in photopolymerization. Those skilled in the art can understand how to obtain a polymer with the desired molecular weight based on the description in this application, including the specific examples described below, and the technical common sense at the time of filing this application.

[0145] In the reinforcing film disclosed herein, the amount of polymer (B) used relative to the amount of polymer (A) per 100 parts by weight can be, for example, 0.1 parts by weight or more. From the viewpoint of obtaining a higher effect (preferably, light peeling resistance in the initial stage of adhesion), it is preferable to use 0.2 parts by weight or more. In some embodiments, from the viewpoint of improving reprocessability, the amount of polymer (B) used is appropriately set to 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and can be set to 0.8 parts by weight or more, or 1.0 parts by weight or more, or 1.5 parts by weight or more, or 2.0 parts by weight or more, or 3.0 parts by weight or more, 4.0 parts by weight or more, or 5.0 parts by weight or more. Furthermore, the amount of polymer (B) used relative to the amount of polymer (A) per 100 parts by weight can be, for example, 75 parts by weight or less, or 30 parts by weight or less, or 20 parts by weight or less. It can also be 15 parts by weight or less, or 10 parts by weight or less. From the viewpoint of easily improving the adhesion after the initial increase in adhesive strength, in some embodiments, the amount of polymer (B) used relative to 100 parts by weight of polymer (A) is preferably 8.0 parts by weight or less, more preferably 5.0 parts by weight or less, even more preferably 4.5 parts by weight or less, and can be 3.5 parts by weight or less, 3.0 parts by weight or less, or 2.5 parts by weight or less (e.g., 2.0 parts by weight or less). By setting the amount of polymer (B) within the above range, it is possible to better balance the initial peel strength and the increase in adhesive strength, and to easily improve flexibility (especially flexibility in low-temperature regions).

[0146] The adhesive layer may, as needed, contain polymers other than polymer (A) and polymer (B) (any polymer) without significantly impairing the performance of the reinforcing film disclosed herein. As non-limiting examples of such arbitrary polymers, in addition to rubber-based polymers, polyester-based polymers, urethane-based polymers, polyether-based polymers, silicone-based polymers, polyamide-based polymers, fluoropolymers, etc., known in the adhesive field, acrylic polymers that are not equivalent to any of polymers (A) and polymer (B) may also be listed. The amount of the aforementioned arbitrary polymer used is typically suitably set to 20% by weight or less of the total polymer component contained in the adhesive layer, and may be 15% by weight or less, or 10% by weight or less. In some embodiments, the amount of the aforementioned arbitrary polymer used may be 5% by weight or less, 3% by weight or less, or 1% by weight or less of the total polymer component. An adhesive layer that substantially does not contain polymers other than polymer (A) and polymer (B) may also be used.

[0147] (Zirconium-containing compounds)

[0148] In addition to the polymers (A) and (B) described above, the adhesive layer disclosed herein also contains a zirconium (Zr)-containing compound. By appropriately using a Zr-containing compound, good flexibility (especially in low-temperature regions), initial easy peeling, and high adhesion after the adhesive strength increases can be achieved. One Zr-containing compound can be used alone or in combination of two or more. Preferably, the Zr-containing compound is an organozirconium-containing compound; for example, one or more compounds selected from Zr-containing organometallic catalysts (typically organic compounds having Zr at the active site) can be used as the Zr-containing compound in the disclosed technology.

[0149] As Zr-containing compounds (organic zirconium-containing compounds), there are no particular limitations; examples include: zirconium tetraacetylacetonate, zirconium monoacetylacetonate, zirconium ethyl acetoacetate, zirconium octanoate, etc. More specifically, examples include: tetraethoxyzirconium, tetra-n-propoxyzirconium, tetraisopropoxyzirconium, tetra-n-butoxyzirconium (n-butyl zirconate), tetraisobutoxyzirconium, tetra-sec-butoxyzirconium, tetra-tert-butoxyzirconium, etc., as well as triethoxymono(acetylacetonate)zirconium, tri-n-propoxymono(acetylacetonate)zirconium, triisopropoxymono(acetylacetonate)zirconium, tri-n-butoxymono(acetylacetonate)zirconium, tri-sec-butoxymono(acetylacetonate)zirconium, tri-tert-butoxymono(acetylacetonate)zirconium, diethoxybis(acetylacetonate)zirconium, di-n-propoxy... Zirconium bis(acetylacetone), diisopropoxyzirconium bis(acetylacetone), di-n-butoxyzirconium bis(acetylacetone), di-sec-butoxyzirconium bis(acetylacetone), di-tert-butoxyzirconium bis(acetylacetone), monoethoxytri(acetylacetone), mono-n-propoxytri(acetylacetone), monoisopropoxytri(acetylacetone), mono-n-butoxytri(acetylacetone), mono-sec-butoxytri(acetylacetone), mono-tert-butoxytri(acetylacetone), tetra(acetylacetone), triethoxymono(ethyl acetoacetate)zirconium Zirconium chelates including tri-n-propoxy mono(ethyl acetoacetate)zirconium, tri-isopropoxy mono(ethyl acetoacetate)zirconium, tri-n-butoxy mono(ethyl acetoacetate)zirconium, tri-sec-butoxy mono(ethyl acetoacetate)zirconium, tri-tert-butoxy mono(ethyl acetoacetate)zirconium, diethoxybis(ethyl acetoacetate)zirconium, di-n-propoxybis(ethyl acetoacetate)zirconium, di-isopropoxybis(ethyl acetoacetate)zirconium, di-n-butoxybis(ethyl acetoacetate)zirconium, di-sec-butoxybis(ethyl acetoacetate)zirconium, di-tert-butoxybis(ethyl acetoacetate)zirconium, monoethoxytri(ethyl acetoacetate)zirconium, mono-n-propoxytri(ethyl acetoacetate)zirconium, monoisopropoxytri(ethyl acetoacetate)zirconium, mono-n-butoxytri(ethyl acetoacetate)zirconium, mono-sec-butoxytri(ethyl acetoacetate)zirconium, mono-tert-butoxytri(ethyl acetoacetate)zirconium, tetra(ethyl acetoacetate)zirconium, mono(acetylacetone)tri(ethyl acetoacetate)zirconium, bis(acetylacetone)bis(ethyl acetoacetate)zirconium, tri(acetylacetone)mon(ethyl acetoacetate)zirconium, etc. The aforementioned organozirconium-containing compounds can be used alone or in combination of two or more.

[0150] The preferred amount of the Zr-containing compound can be based on the amount of polymer (A) used and the amount W of monomer units derived from nitrogen-containing monomers contained in polymer (A). N To set. In some schemes, the amount W of the Zr-containing compound. Zr [Parts by weight] The amount W of monomer units derived from nitrogen-containing monomers in 100 parts by weight of polymer (A) relative to polymer (A). N Regarding the relationship of [parts by weight], the above W N[Parts by weight] relative to the above W Zr The ratio of [parts by weight] (W) N / W Zr The amount is 4 or more. The adhesive layer contains a Zr-containing compound, and the above W... N [Parts by weight] relative to the above W Zr The ratio of [parts by weight] (W) N / W Zr If the value is 4 or higher, then by passing W N In a composition limited to 14 parts by weight or less that is suitable for improving flexibility (especially flexibility in low-temperature regions), both initial easy peeling and high adhesion after the adhesion strength increases can be taken into account. While not intended to be theoretically constrained, as a reason for achieving such an effect, it is believed that in adhesives comprising polymers (A) and (B) containing monomer units derived from nitrogen-containing monomers, and a Zr-containing compound, the Zr-containing compound has the effect of readily attracting the polymer (A) to the surface of the substrate (e.g., a polyimide film). This effect becomes apparent after adhesion to the substrate over time and / or by heating, and is further enhanced by the ratio (W... N / W Zr Setting it to an appropriate range helps to improve the adhesive strength after the increase in adhesive strength. However, it is not limited to this reason alone.

[0151] From the perspective of better utilizing the effect of increased adhesive strength (e.g., adhesive strength N2 after heating), in some solutions, compared to (W) N / W Zr The value should be 5 or higher, preferably 7 or higher, and ideally 9 or higher. For example, it can be 10 or higher, 12 or higher, 14 or 16 or higher. (W) N / W Zr There is no particular upper limit to ), and it can be appropriately set within the range of achieving the desired effect. In some schemes, it is more than (W) N / W Zr For example, it can be below 2000, below 1400, below 1000, below 700, below 500, below 300, below 250, or below 200.

[0152] Furthermore, in some embodiments where polymer (A) comprises monomer units derived from monomers having a ring containing nitrogen atoms, the amount W of the aforementioned monomer units derived from monomers having a ring containing nitrogen atoms contained in 100 parts by weight of polymer (A) is... RN [Parts by weight] relative to the above W Zr The ratio of [parts by weight] (i.e., the ratio (W)) RN / W Zr The lower limit of (W) can be determined by the ratio mentioned above.N / W Zr Any of the lower bound values ​​of ). Furthermore, in some schemes, as the aforementioned ratio (W) RN / W Zr The upper limit of (W) can be determined by the above ratio. N / W Zr Any of the lower bound values ​​of ).

[0153] The amount W of Zr-containing compounds Zr The amount of Zr-containing compound W is not particularly limited to 100 parts by weight of polymer (A), and can be set in the range of approximately 0.0001 parts by weight to 3 parts by weight. In some embodiments, the amount of Zr-containing compound W... Zr For example, it can be set to 0.001 parts by weight or more, 0.005 parts by weight or more, or 0.008 parts by weight or more. In schemes where Zr-containing compounds can also function as crosslinking catalysts (e.g., in schemes where the adhesive layer includes an isocyanate-based crosslinking agent), the amount W of the Zr-containing compound is adjusted accordingly. Zr With increased concentration, there is a tendency for the cross-linking promoting effect to be better exerted. From this perspective, in some schemes, the amount W of the aforementioned Zr-containing compounds... Zr The amount can be 0.01 parts by weight or more, 0.03 parts by weight or more, 0.05 parts by weight or more, or 0.1 parts by weight or more. Furthermore, the amount W of the Zr-containing compound... Zr The amount of polymer (A) is preferably 2 parts by weight or less, more preferably 1.5 parts by weight or less (e.g., 1 part by weight or less, 0.7 parts by weight or less, or 0.5 parts by weight or less), relative to 100 parts by weight of polymer (A), and can be set to a ratio (W) N / W Zr The concentration of Zr is 4 or higher (e.g., 5 or higher, 7 or higher, or 9 or higher). The amount of the aforementioned Zr-containing compounds should be appropriately limited. Zr From the perspective of increased adhesion and flexibility, it becomes advantageous.

[0154] It should be noted that, for purposes such as promoting cross-linking reactions, the adhesive layer disclosed herein may also contain one or more metal compounds (typically organometallic catalysts) other than Zr-containing compounds. Examples of such metal compounds include: tin (Sn)-containing compounds (tin-based catalysts), titanium (Ti)-containing compounds (titanium-based catalysts), hafnium (Hf)-containing compounds (hafnium-based catalysts), iron (Fe)-containing compounds (iron-based catalysts), aluminum (Al)-containing compounds (aluminum-based catalysts), zinc (Zn)-containing compounds (zinc-based catalysts), and bismuth (Bi)-containing compounds (bismuth-based catalysts). In some embodiments, the amount of metal compound other than Zr-containing compounds used, by weight, is appropriately set to be less than the amount of Zr-containing compounds used (i.e., less than 1 times the amount of Zr-containing compounds used), preferably less than 0.5 times, more preferably less than 0.3 times or less than 0.1 times. Alternatively, metal compounds other than Zr-containing compounds may not be used.

[0155] (Cross-linking agent)

[0156] In the adhesive layer, crosslinking agents can be used as needed for purposes such as adjusting cohesion. Crosslinking agents known in the adhesive field can be used, such as epoxy crosslinking agents, isocyanate crosslinking agents, silicone crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, silane crosslinking agents, and alkyl etherified melamine crosslinking agents. Isocyanate crosslinking agents and epoxy crosslinking agents are preferred. In some solutions, isocyanate crosslinking agents are preferred as they are suitable for balancing adhesion improvement and flexibility. One crosslinking agent can be used alone, or two or more can be used in combination.

[0157] As isocyanate-based crosslinking agents, polyfunctional isocyanates (compounds having an average of two or more isocyanate groups per molecule, including compounds with isocyanurate structures) are preferred. Isocyanate-based crosslinking agents can be used alone or in combination of two or more.

[0158] Examples of polyfunctional isocyanates include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates.

[0159] Specific examples of aliphatic polyisocyanates include: 1,2-ethylene diisocyanate; tetramethylene diisocyanates such as 1,2-tetramethylene diisocyanate, 1,3-tetramethylene diisocyanate, and 1,4-tetramethylene diisocyanate; hexamethylene diisocyanates such as 1,2-hexamethylene diisocyanate, 1,3-hexamethylene diisocyanate, 1,4-hexamethylene diisocyanate, 1,5-hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, and 2,5-hexamethylene diisocyanate; 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, and lysine diisocyanate.

[0160] Specific examples of alicyclic polyisocyanates include: isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; cyclopentyl diisocyanates such as 1,2-cyclopentyl diisocyanate and 1,3-cyclopentyl diisocyanate; hydrogenated phenyl dimethyl diisocyanate, hydrogenated toluene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tetramethylxylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0161] Specific examples of aromatic polyisocyanates include: 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenyl ether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, and 2,2'-diphenylpropane-4,4'-diisocyanate. -Diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, terephthalene diisocyanate, naphthalene-1,4-diisocyanate, naphthalene-1,5-diisocyanate, 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, phenylenedimethyl-1,4-diisocyanate, phenylenedimethyl-1,3-diisocyanate, etc.

[0162] Preferred polyfunctional isocyanates include, for example, polyfunctional isocyanates having an average of three or more isocyanate groups per molecule. These trifunctional or higher isocyanates can be polymers (e.g., dimers or trimers) of difunctional or higher isocyanates, derivatives (e.g., addition reaction products of polyols with two or more molecules of polyfunctional isocyanates), polymers, etc. Examples include: dimers and trimers of diphenylmethane diisocyanate, isocyanurates of hexamethylene diisocyanate (trimeric adducts of isocyanurate structures), reaction products of trimethylolpropane and toluene diisocyanate, reaction products of trimethylolpropane and hexamethylene diisocyanate, trimethylolpropane adduct of phenyl diisocyanate, trimethylolpropane adduct of isophorone diisocyanate, trimethylolpropane adduct of hexamethylene diisocyanate, polymethylene polyphenyl isocyanate, polyether polyisocyanate, polyester polyisocyanate, and their adducts with various polyols, as well as polyfunctional isocyanates such as polyisocyanates with multifunctionalized isocyanurate bonds, biuret bonds, urethane bonds, etc.

[0163] Commercially available examples of the aforementioned polyfunctional isocyanates include: Asahi Kasei Chemicals' "DURANATE TPA-100"; TOSOH's "CORONATE L", "CORONATE HL", "CORONATE HK", "CORONATE HX", and "CORONATE 2096"; and Mitsui Chemicals' "TAKENATE D110N", "TAKENATE D120N", "TAKENATE D140N", and "TAKENATE D160N".

[0164] Examples of epoxy crosslinking agents include: bisphenol A, epichlorohydrin-type epoxy resins, ethylene glycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,6-hexanediol glycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl aniline, diamine glycidylamine, N,N,N',N'-tetraglycidyl-m-phenylenediamine, and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane. They can be used alone or in combination of two or more.

[0165] When using a crosslinking agent, the amount used is not particularly limited; for example, it can be set to more than 0 parts by weight relative to 100 parts by weight of polymer (A). Furthermore, the amount of crosslinking agent used relative to 100 parts by weight of polymer (A) can be, for example, 0.01 parts by weight or more, preferably 0.05 parts by weight or more. By increasing the amount of crosslinking agent used, there is a tendency to suppress the adhesive force in the initial bonding stage and improve reprocessability. In some embodiments, the amount of crosslinking agent used relative to 100 parts by weight of polymer (A) can be 0.07 parts by weight or more, 0.1 parts by weight or more, or 0.15 parts by weight or more. On the other hand, from the viewpoint of moderately allowing the movement of polymer (B) to achieve an increase in adhesive force after heating, the amount of crosslinking agent used relative to 100 parts by weight of polymer (A) is generally appropriately set to 15 parts by weight or less, and can be 10 parts by weight or less, or 5 parts by weight or less.

[0166] The technology disclosed herein is preferably implemented using at least an isocyanate-based crosslinking agent as the crosslinking agent. From the viewpoint of balancing good reprocessability in the initial bonding stage and increased adhesive strength after heating, in some embodiments, the amount of isocyanate-based crosslinking agent used relative to 100 parts by weight of polymer (A) can be, for example, 0.01 parts by weight or more, preferably 0.05 parts by weight or more, more preferably 0.07 parts by weight or more, and can be 0.10 parts by weight or more, or 0.15 parts by weight or more (e.g., 0.20 parts by weight or more). By increasing the amount of isocyanate-based crosslinking agent used, moderate cohesive strength can be obtained, with a tendency for initial light peeling and excellent processability. Furthermore, the amount of isocyanate-based crosslinking agent used relative to 100 parts by weight of polymer (A) can be, for example, 5 parts by weight or less, preferably less than 1.0 parts by weight, more preferably less than 0.5 parts by weight, and even more preferably less than 0.3 parts by weight, and can be 0.2 parts by weight or less (e.g., less than 0.2 parts by weight) or 0.15 parts by weight or less (e.g., less than 0.15 parts by weight). Moderately limiting the amount of isocyanate-based crosslinking agents is advantageous from the viewpoint of improving the flexibility of the adhesive, and it is also easy to obtain an increase in adhesive strength after heating.

[0167] (Tackifying resin)

[0168] The adhesive layer may include a tackifying resin as needed. There are no particular limitations on the tackifying resin; examples include: rosin-based tackifying resins, terpene-based tackifying resins, phenol-based tackifying resins, hydrocarbon-based tackifying resins, ketone-based tackifying resins, polyamide-based tackifying resins, epoxy-based tackifying resins, and elastic system tackifying resins. One tackifying resin may be used alone, or two or more may be used in combination.

[0169] The content of the tackifying resin is not particularly limited and can be set to achieve appropriate adhesive properties depending on the purpose and application. The content of the tackifying resin (the total amount of two or more tackifying resins) relative to 100 parts by weight of polymer (A) can be, for example, about 0.5 to 200 parts by weight, or about 0.5 to 100 parts by weight, or about 0.5 to 50 parts by weight. Furthermore, the technology disclosed herein can preferably be implemented by limiting the amount of tackifying resin used. For example, the content of the tackifying resin relative to 100 parts by weight of polymer (A) can be less than 20 parts by weight, less than 10 parts by weight, less than 3 parts by weight, or less than 1 part by weight (0 parts by weight to less than 1 part by weight). In some embodiments, the adhesive layer substantially does not contain tackifying resin.

[0170] Furthermore, the adhesive layer in the disclosed technology may, as needed, include leveling agents, plasticizers, softeners, colorants (dyes, pigments, etc.), fillers, antistatic agents, anti-aging agents, ultraviolet absorbers, antioxidants, light stabilizers, preservatives, and other known additives that can be used in adhesives, without significantly impairing the effects of the present invention.

[0171] The adhesive layer constituting the reinforcing film disclosed herein can be a cured layer of the adhesive composition. That is, this adhesive layer can be formed by applying (e.g., coating) a water-dispersible, solvent-based, photocurable, or hot-melt adhesive composition to a suitable surface and then performing a curing treatment. When two or more curing treatments (drying, crosslinking, polymerization, cooling, etc.) are performed, they can be carried out simultaneously or in multiple stages. For adhesive compositions using a partial polymer (polymer slurry) of monomer raw materials, a final copolymerization reaction is typically performed as the aforementioned curing treatment. That is, a portion of the polymer is subjected to a further copolymerization reaction to form a complete polymer. For example, if it is a photocurable adhesive composition, light irradiation is performed. Crosslinking, drying, or other curing treatments may also be performed as needed. For example, if it is a photocurable adhesive composition and drying is required, it is preferable to perform photocuring after drying. For adhesive compositions using a complete polymer, drying (heat drying), crosslinking, or other treatments are typically performed as the aforementioned curing treatment as needed.

[0172] The coating of the adhesive composition can be carried out using commonly used coating machines such as gravure roller coaters, reverse roller coaters, licker coaters, dip roller coaters, bar coaters, doctor blade coaters, and spray coaters.

[0173] The thickness of the adhesive layer is not particularly limited; for example, it can be 6 μm or more. In some designs, the thickness of the adhesive layer can be 8 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, or even more than 20 μm. Increasing the thickness of the adhesive layer tends to increase the adhesive strength after heating. Furthermore, in some designs, the thickness of the adhesive layer can be, for example, 300 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 70 μm or less, 50 μm or less, or 40 μm or less. A less excessively thick adhesive layer is advantageous from the viewpoints of thinning the reinforcing film and preventing cohesive failure of the adhesive layer. A reinforcing film with an adhesive layer within the above-mentioned thickness range can achieve a balance between adhesive properties such as adhesive strength and flexibility. It should be noted that when a reinforcing film with a first adhesive layer and a second adhesive layer is provided on both the first and second sides of the substrate, the thickness of the adhesive layer can be at least the thickness of the first adhesive layer. The thickness of the second adhesive layer can also be selected from the same range. Furthermore, in the case of a reinforcing film without a substrate, the thickness of the reinforcing film is consistent with the thickness of the adhesive layer.

[0174] (-20℃ energy storage modulus (G') -20 ))

[0175] In some embodiments of the disclosed technology, the storage modulus (hereinafter sometimes referred to as "storage modulus (G')" of the adhesive constituting the adhesive layer at -20°C is... -20 For example, it can be 10000 kPa, appropriately below 5000 kPa, advantageously below 3000 kPa, and preferably below 1000 kPa. This is achieved by adjusting the energy storage modulus (G'). -20 The storage modulus (G') is limited to a specified value, allowing the adhesive to exhibit good flexibility suitable for repeated bending and flexing. From the viewpoint of further improving flexibility, in some solutions, the storage modulus (G') of the adhesive is... -20 The pressure is preferably below 700 kPa, more preferably below 500 kPa, and even more preferably below 300 kPa. It can also be below 200 kPa, below 150 kPa, below 140 kPa, below 130 kPa, below 120 kPa, or below 110 kPa. The storage modulus (G') of the adhesive... -20 There is no particular limitation on the lower limit of the energy storage modulus (G'). For example, it can be above 20 kPa or above 30 kPa. In some schemes, considering the ease of balancing other properties (such as low initial adhesion N1, high adhesion after heating, and one or more of the high rise rate N2 / N1), the energy storage modulus (G') of the adhesive is considered. -20For example, it can be above 50 kPa, above 70 kPa, above 80 kPa, above 90 kPa, or above 100 kPa.

[0176] (23℃ energy storage modulus (G') 23 ))

[0177] The storage modulus of the adhesive at 23°C (hereinafter sometimes expressed as "storage modulus (G')"). 23 There are no particular limitations, but it is preferred to have a high energy storage modulus (G'). -20 The value falls within the range below any of the upper limits mentioned above. In some schemes, the storage modulus (G') of the adhesive is... 23 The appropriate setting is below 200 kPa. Adhesives with a storage modulus (G'23) below the specified value generally exhibit excellent strain mitigation properties in the room temperature range, and also readily show an increase in adhesive strength. 23 The pressure is preferably 130 kPa or less, more preferably 80 kPa or less. In some preferred embodiments, the above-mentioned bulk modulus G' 23 It can be below 50 kPa, or below 40 kPa (for example, below 35 kPa).

[0178] In some schemes, the storage modulus (G') of the adhesive 23 The energy storage modulus (G') is appropriately set to above 10 kPa. 23 When the value is set above the specified value, the initial adhesive force is easily within a suitable range for excellent light peel performance. The aforementioned storage modulus (G') 23 The pressure is preferably 15 kPa or higher, more preferably 20 kPa or higher, and can be 25 kPa or higher, or 30 kPa or higher.

[0179] (80℃ energy storage modulus (G') 80 ))

[0180] The storage modulus of the adhesive at 80°C (hereinafter, sometimes expressed as "storage modulus (G')"). 80 There are no particular limitations, but it is preferred to have a high energy storage modulus (G'). -20 The value falls within the range below any of the upper limits mentioned above. In some schemes, the storage modulus (G') of the adhesive layer... 80 The pressure is appropriately set to below 100 kPa, preferably below 70 kPa, more preferably below 50 kPa, and can be below 30 kPa or below 20 kPa.

[0181] In some schemes, the storage modulus (G') of the adhesive layer 80 The appropriate pressure is above 1 kPa, preferably above 2 kPa. The above-mentioned energy storage modulus (G') 80A value above a specified value becomes advantageous from the viewpoint of the adhesive's heat resistance (e.g., adhesive properties in high-temperature regions). In some preferred embodiments, the aforementioned storage modulus (G') is... 80 For example, it can be above 3 kPa, above 5 kPa, above 7 kPa, above 9 kPa, or above 10 kPa.

[0182] The storage modulus of the adhesive layer at various temperatures can be adjusted based on the type and properties (molecular weight, glass transition temperature, molecular structure, etc.) of polymer (A); the type (chemical structure, etc.) and properties (molecular weight, glass transition temperature, etc.) of polymer (B); the amount used; and the type and amount of crosslinking agent. The storage modulus (G') of the adhesive layer at -20℃... -20 The energy storage modulus was determined using the method described in the examples described later. The energy storage modulus at other temperatures can also be determined using the same method.

[0183] <Supporting substrate>

[0184] Some reinforcing films can be in the form of adhesive sheets with adhesive layers on one or both sides of the supporting substrate. The material of the supporting substrate is not particularly limited and can be appropriately selected depending on the intended use and application of the reinforcing film. Non-limiting examples of usable substrates include: resin films such as plastic films; foam sheets formed from foams such as polyurethane foam, polyethylene foam, and polychloroprene foam; woven and non-woven fabrics made from various fibrous materials (such as natural fibers like hemp and cotton; synthetic fibers like polyester and vinylon; semi-synthetic fibers like acetate, etc.) alone or in blends; paper types such as Japanese paper, high-grade paper, kraft paper, and crepe paper; metal foils such as aluminum foil and copper foil; etc. Substrates composed of these composites can also be used. Examples of such composite substrates include: substrates with structures formed by laminating metal foil with the aforementioned plastic films, and plastic substrates reinforced with inorganic fibers such as glass cloth.

[0185] As the substrate for the reinforcing membrane disclosed herein, various membrane substrates can be preferably used. These membrane substrates can be porous substrates such as foamed membranes or nonwoven sheets, or non-porous substrates, or substrates with a structure consisting of layers of porous and non-porous materials. In some embodiments, as the membrane substrate, a substrate comprising a self-supporting or non-dependent resin membrane capable of independently maintaining its shape can be preferably used as the base membrane. Here, "resin membrane" refers to a non-porous structure, typically a resin membrane that is substantially free of air bubbles (pore-free). Therefore, the resin membrane is a concept distinct from foamed membranes and nonwoven fabrics. As the resin membrane, a self-supporting or non-dependent resin membrane capable of independently maintaining its shape can be preferably used. The resin membrane can be a single-layer structure or a multi-layer structure with two or more layers (e.g., a three-layer structure).

[0186] Resin materials constituting the resin film can be, for example, polyester, polyolefin, nylon 6, nylon 66, polyamide (PA) such as partially aromatic polyamides, polyimide (PI), polyamide-imide (PAI), polyetheretherketone (PEEK), polyethersulfone (PES), polyphenylene sulfide (PPS), polycarbonate (PC), polyurethane (PU), ethylene-vinyl acetate copolymer (EVA), polytetrafluoroethylene (PTFE) and other fluoropolymers, acrylic resins, polyacrylates, polystyrene, polyvinyl chloride, polyvinylidene chloride and other resins. The resin film can be a resin film formed using a resin material containing only one such resin, or a resin film formed using a blend of two or more resin materials. The resin film can be unstretched or stretched (e.g., uniaxially or biaxially stretched).

[0187] Preferred examples of resin materials constituting resin films include: polyimide resins, polyester resins, PPS resins, and polyolefin resins. Here, polyimide resins refer to resins containing polyimide in a proportion exceeding 50% by weight. Similarly, polyester resins refer to resins containing polyester in a proportion exceeding 50% by weight, PPS resins refer to resins containing PPS in a proportion exceeding 50% by weight, and polyolefin resins refer to resins containing polyolefins in a proportion exceeding 50% by weight.

[0188] Specific examples of polyester resins include: polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), and polybutylene naphthalate.

[0189] As a polyolefin resin, a single polyolefin or a combination of two or more polyolefins can be used. This polyolefin can be, for example, a homopolymer of an α-olefin, a copolymer of two or more α-olefins, or a copolymer of one or more α-olefins with other vinyl monomers. Specific examples include: polyethylene (PE), polypropylene (PP), poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene rubber (EPR), ethylene-propylene-butene copolymers, ethylene-butene copolymers, ethylene-vinyl alcohol copolymers, and ethylene-ethyl acrylate copolymers. Any type of low-density (LD) polyolefin and high-density (HD) polyolefin can be used. Examples of polyolefin resin films include: unstretched polypropylene (CPP) film, biaxially oriented polypropylene (OPP) film, low-density polyethylene (LDPE) film, linear low-density polyethylene (LLDPE) film, medium-density polyethylene (MDPE) film, high-density polyethylene (HDPE) film, polyethylene (PE) film made by blending two or more types of polyethylene (PE), and PP / PE blend film made by blending polypropylene (PP) and polyethylene (PE), etc.

[0190] Specific examples of resin films that can be preferably used as the base film for the reinforcing films disclosed herein include: PI film, PET film, PEN film, PPS film, PEEK film, CPP film, and OPP film.

[0191] In the resin film, known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, slip agents, and antiblocking agents can be added as needed, without significantly impairing the effects of the present invention. The amount of additives is not particularly limited and can be appropriately set according to the intended purpose, etc.

[0192] There are no particular limitations on the manufacturing method of the resin film. For example, conventional resin film forming methods known in the past, such as extrusion molding, blow molding, T-die casting, and calendering roll forming, can be appropriately used.

[0193] The aforementioned substrate may be a substrate substantially composed of such a base film. Alternatively, the aforementioned substrate may also be a substrate that includes auxiliary layers in addition to the aforementioned base film. Examples of such auxiliary layers include: optical property adjustment layers (e.g., coloring layers, anti-reflective layers), printing layers for imparting a desired appearance to the substrate, laminated layers, antistatic layers, primer layers, release layers, and other surface treatment layers.

[0194] The thickness of the substrate is not particularly limited and can be selected according to the intended use and application method of the reinforcing film. For example, the substrate thickness can be 1000 μm or less. In some applications, considering the operability and processability of the reinforcing film, the substrate thickness can be, for example, 500 μm or less, 300 μm or less, 250 μm or less, or 200 μm or less. Considering the miniaturization and lightweighting of products using the reinforcing film, in some applications, the substrate thickness can be, for example, 160 μm or less, 130 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 25 μm or less, 10 μm or less, or 5 μm or less. If the substrate thickness is reduced, there is a tendency for the reinforcing film to have increased flexibility and adaptability to the surface shape of the adhered object. Furthermore, from the perspective of operability and processability, the thickness of the substrate can be, for example, 2 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 25 μm or more, or even more than 25 μm. In some solutions, the thickness of the substrate can be, for example, 30 μm or more, 35 μm or more, 55 μm or more, 70 μm or more, 75 μm or more, 90 μm or more, or even 120 μm or more. From the perspective of enhancing performance, in some solutions, a substrate with a thickness of 30 μm or more (e.g., 45 μm or more, 55 μm or more, or 65 μm or more) is preferred.

[0195] Conventional surface treatments, such as corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, and primer coating based on a primer, can be applied to the first surface of the substrate as needed. Such surface treatments can be used to improve the anchoring strength of the adhesive layer to the substrate. For example, in a reinforcing film having a substrate containing a resin film as a base film, a substrate that has undergone this anchoring strength improvement treatment is preferred. The above surface treatments can be applied individually or in combination. The composition of the primer used in the formation of the primer coating is not particularly limited, and can be appropriately selected from known primers. The thickness of the primer coating is not particularly limited, but is typically suitable at around 0.01 μm to 1 μm, preferably around 0.1 μm to 1 μm. Other treatments that can be applied to the first surface of the substrate as needed include: antistatic layer formation treatment, coloring layer formation treatment, and printing treatment.

[0196] In the case of a single-sided adhesive sheet with an adhesive layer on only the first side of the substrate, the reinforcing film disclosed herein can be subjected to conventional surface treatments such as peeling treatment and antistatic treatment on the second side of the substrate as needed. For example, by surface treating the back side of the substrate with a peeling agent (typically by providing a peeling layer based on the peeling agent), the unwinding force of the reinforcing film wound into a roll can be reduced. As peeling agents, silicone-based peeling agents, long-chain alkyl-based peeling agents, olefin-based peeling agents, fluorinated peeling agents, fatty acid amide-based peeling agents, molybdenum sulfide, silica powder, etc., can be used. In addition, for purposes such as improving printability, reducing light reflectivity, and improving re-adhesion, the second side of the substrate can also be treated with corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, etc. In the case of a double-sided adhesive sheet, the second side of the substrate can be subjected to the same surface treatments as those exemplified above, which are surface treatments that can be applied to the first side of the substrate, as needed. It should be noted that the surface treatment applied to the first side of the substrate can be the same as or different from the surface treatment applied to the second side.

[0197] <Enhancing the properties of membranes>

[0198] The initial adhesive force N1, measured after the reinforcing film disclosed herein is preferably bonded to a polyimide film and held at 23°C for 30 minutes, is limited to a specified value or less. In some embodiments, the adhesive force N1 is, for example, suitably less than 500 gf / 25 mm, advantageously less than 300 gf / 25 mm, preferably less than 200 gf / 25 mm or 180 gf / 25 mm, more preferably less than 150 gf / 25 mm or 130 gf / 25 mm, further preferably less than 110 gf / 25 mm or 100 gf / 25 mm, and can be less than 90 gf / 25 mm or 80 gf / 25 mm. A low adhesive force N1 is preferred from the viewpoint of reprocessability. There is no particular limitation on the lower limit of the adhesive force N1, for example, it can be more than 1 gf / 25 mm. From the viewpoints of workability of the adhered object and prevention of positional displacement before the adhesive force increases, the adhesive force N1 is generally suitable to be more than 10 gf / 25 mm. Considering the improvement of adhesion after heating, in some solutions, the adhesion force N1 can be above 20gf / 25mm, or above 30gf / 25mm, or above 50gf / 25mm, or above 60gf / 25mm, or above 70gf / 25mm.

[0199] The adhesive force N1 [gf / 25mm] is understood as follows: after pressing a polyimide film, which is the adherend, into the film and placing it in an environment of 23°C and 50% RH for 30 minutes, the 180° peel adhesive force is measured under the same conditions (i.e., at 23°C) with a peel angle of 180° and a tensile speed of 300mm / min. From the viewpoint of workability, the polyimide film, which is the adherend, can be used in the form of a measuring polyimide plate (a plate-shaped adherend having a surface formed by the polyimide film) formed by fixing the polyimide film to a support plate (glass plate, stainless steel plate, etc.). During the measurement, an appropriate backing material (e.g., a PET film with a thickness of about 25μm) can be pasted onto the reinforcing film of the test object as needed for reinforcement. More specifically, the adhesive force N1 can be measured according to the method for measuring the initial adhesive force described in the examples described later.

[0200] The reinforcing film disclosed herein is a film whose adhesive strength increases upon heating. For example, after being bonded to a polyimide film as an adherend and heated at 60°C for 1 hour, followed by holding at 23°C for 30 minutes, the post-heating adhesive strength N2 is appropriately 800 gf / 25 mm or more, advantageously 950 gf / 25 mm or more, and preferably 1000 gf / 25 mm or more. The reinforcing film satisfying this characteristic, upon being bonded to the adherend, experiences an increase in adhesive strength to a predetermined value or more upon heating. According to the technology disclosed herein, strong adhesive strength can be obtained through heating. In some embodiments, the adhesive strength N2 is more preferably 1100 gf / 25 mm or more, further preferably 1200 gf / 25 mm or more, and can be 1300 gf / 25 mm or more, or even 1400 gf / 25 mm or more. There is no particular limitation on the upper limit of the adhesive strength N2. From the viewpoint of easily balancing the flexibility of the adhesive layer (especially in low-temperature regions) and initial light peelability, in some solutions, the adhesive force N2 can be, for example, below 4000gf / 25mm, below 3500gf / 25mm, below 3000gf / 25mm, below 2000gf / 25mm, below 1800gf / 25mm, or below 1600gf / 25mm.

[0201] The adhesive force N2 [gf / 25mm] is understood as follows: after pressing a polyimide film, which is the substrate, into the film and holding it at 60°C for 60 minutes, followed by placing it at 23°C and 50% RH for 30 minutes, the 180° peel adhesive force is measured under the same conditions as the adhesive force N1, with a peel angle of 180° and a tensile speed of 300mm / min. As the substrate, a polyimide film (which can be in the form of a polyimide sheet as described above) is used (similar to the adhesive force N1). During the measurement, a suitable backing material (e.g., a PET film with a thickness of approximately 25μm) can be applied to the reinforcing film of the test object as needed for reinforcement. More specifically, the adhesive force N2 can be measured according to the method for measuring the adhesive force after heating described in the following examples.

[0202] The rate of increase in adhesive strength N2 [gf / 25mm] after heating relative to the initial adhesive strength N1 [gf / 25mm], i.e., the adhesive strength increase rate N2 / N1 [%), is not particularly limited. For example, it can be 160% or more, or 250% or more, 500% or more, or 750% or more. In some embodiments, N2 / N1 is appropriately 850% or more, preferably 900% or more, more preferably 950% or more, and even more preferably 1000% or more. It can be 1200% or more, or 1400% or more, or 1500% or more, 1600% or more, 1700% or more, or 1800% or more. Reinforcing films with a high N2 / N1 exhibit good reprocessability in the initial stage of bonding, and the adhesive strength increases significantly through subsequent heating, etc. The upper limit of N2 / N1 is not particularly limited, for example, it can be 10000% or less, 7000% or less, or 5000% or less. From the viewpoint of easily balancing the flexibility of the adhesive (especially in low-temperature regions), in some solutions, N2 / N1 can be, for example, below 4000%, below 3000%, below 2500%, or below 2000%.

[0203] It should be noted that the adhesive strength of the reinforcing film after heating disclosed herein represents a characteristic of the reinforcing film and does not limit its application. In other words, the application of the reinforcing film disclosed herein is not limited to heating at 60°C for 60 minutes; for example, it can also be used in applications where the temperature does not specifically reach room temperature (typically 20°C to 30°C, and more typically 23°C to 25°C). In this application, the adhesive strength increases over a longer period, achieving a strong bond. Furthermore, the reinforcing film disclosed herein can have its adhesive strength increased by heating it at a temperature exceeding 30°C (e.g., around 50 to 70°C) or higher than 60°C at any time after application. The heating temperature in this heating treatment is not particularly limited and can be set considering workability, economy, the substrate of the reinforcing film, the heat resistance of the adhered objects, etc. The aforementioned heating temperature can be, for example, less than 150°C, less than 120°C, less than 100°C, less than 80°C, or less than 70°C. Furthermore, the aforementioned heating temperature can be set to 40°C or higher, 45°C or higher, 50°C or higher, 55°C or higher, 60°C or higher, or 70°C or higher, or 80°C or higher, or 100°C or higher. The heating time is not particularly limited; for example, it can be less than 3 hours, less than 1 hour, less than 30 minutes, or less than 10 minutes. Alternatively, the heating time can be more than 1 minute, more than 15 minutes, more than 30 minutes, or more than 1 hour. Or, a longer heating treatment can be performed within the limit that the reinforcing film and the adhered material do not experience significant thermal degradation. It should be noted that the heating treatment can be performed in one go or in multiple stages.

[0204] <Reinforcing film with substrate>

[0205] When the reinforcing film disclosed herein is in the form of an adhesive sheet with a substrate, the thickness of the reinforcing film can be, for example, 1000 μm or less, 600 μm or less, 350 μm or less, or 250 μm or less. From the viewpoint of miniaturization, lightweighting, and thinning of products using the reinforcing film, in some embodiments, the thickness of the reinforcing film can be, for example, 200 μm or less, 175 μm or less, 160 μm or less, 140 μm or less, or 120 μm or less. The reinforcing film disclosed herein can also be implemented with a thickness of 115 μm or less, 105 μm or less, 95 μm or less, or 85 μm or less. Furthermore, from the viewpoint of operability, the thickness of the reinforcing film can be, for example, 5 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, or 30 μm or more. In some designs, the thickness of the reinforcing membrane can be, for example, 50 μm or more, 60 μm or more, 75 μm or more, 85 μm or more, 90 μm or more, 100 μm or more, or 120 μm or more. There is no particular upper limit to the thickness of the reinforcing membrane.

[0206] It should be noted that the thickness of the reinforcing film refers to the thickness of the portion adhered to the object being bonded. For example, in... Figure 1 In the reinforcement film 1 shown, the thickness refers to the thickness from the adhesive surface 21A of the reinforcement film 1 to the second surface 10B of the substrate 10, excluding the thickness of the release liner 31.

[0207] The reinforcing film disclosed herein is preferably implemented in a configuration where the thickness Ts of the supporting substrate is greater than the thickness Ta of the adhesive layer, i.e., Ts / Ta is greater than 1. Ts / Ta can be, for example, 1.1 or more, 1.2 or more, 1.5 or more, or 1.7 or more, without particular limitation. For example, by increasing Ts / Ta, there is a tendency to achieve good results even when the reinforcing film is thinned. In some embodiments, Ts / Ta can be 2 or more (e.g., greater than 2), 2.5 or more, or 2.8 or more. Furthermore, Ts / Ta can be, for example, 50 or less, or 20 or less. From the viewpoint that high adhesive strength after heating is easily achieved even when the reinforcing film is thinned, Ts / Ta can be, for example, 10 or less, 8 or less, or 5 or less.

[0208] The adhesive layer described above is preferably fixed to the supporting substrate. Here, "fixed" means that, in a reinforcing film where the adhesive force increases after being adhered to the substrate, the adhesive layer exhibits sufficient anchoring to the supporting substrate to the extent that no peeling occurs at the interface between the adhesive layer and the supporting substrate when the reinforcing film is peeled off from the substrate. With a substrate-supported reinforcing film in which the adhesive layer is fixed to the supporting substrate, the adhered object and the supporting substrate can be firmly integrated. As a preferred example of a reinforcing film in which the adhesive layer is fixed to the substrate, a reinforcing film in which no peeling (anchoring failure) occurs between the adhesive layer and the supporting substrate when the adhesive force after heating is measured is given. A reinforcing film in which no anchoring failure occurs when the adhesive force after heating is measured is a preferred example of a reinforcing film in which the adhesive layer is fixed to the substrate.

[0209] The reinforcing film disclosed herein can be more preferably manufactured by a method comprising the following steps: contacting a liquid adhesive composition with a first surface of a substrate; and curing the adhesive composition on the first surface to form an adhesive layer. The curing of the adhesive composition may be accompanied by one or more of the following: drying, crosslinking, polymerization, cooling, etc. Compared to a method of depositing the adhesive layer on the first surface of the substrate by curing the liquid adhesive composition on the first surface, the anchoring strength of the adhesive layer to the substrate is improved by this method. Therefore, it is preferable to manufacture a reinforcing film in which the adhesive layer is fixed to the substrate.

[0210] In some embodiments, as a method for contacting the liquid adhesive composition with the first surface of the substrate, the adhesive composition can be directly applied to the first surface of the substrate. By bringing the first surface (adhesive surface) of the adhesive layer cured on the first surface of the substrate against the release surface, a reinforcing film is formed in which the second surface of the adhesive layer is fixed to the first surface of the substrate, and the first surface of the adhesive layer abuts against the release surface. The release surface can be the surface of the release liner, the back surface of the substrate after the release treatment, etc.

[0211] Furthermore, for example, in the case of a photocurable adhesive composition using a portion of a polymer (polymer slurry) of monomer raw materials, the adhesive composition can be applied to the peel surface and then the applied adhesive composition can be used to cover the first surface of the substrate, thereby bringing the uncured adhesive composition into contact with the first surface of the substrate. In this state, the adhesive composition sandwiched between the first surface of the substrate and the peel surface is irradiated with light to cure it, thereby forming an adhesive layer.

[0212] It should be noted that the methods illustrated above are not limited to the manufacturing method of the reinforcing film disclosed herein. When manufacturing the reinforcing film disclosed herein, one or more suitable methods for bonding the adhesive layer to the first surface of the substrate can be used alone or in combination. Examples of such methods include: a method for curing a liquid adhesive composition on the first surface of the substrate to form an adhesive layer as described above; a method for performing a surface treatment on the first surface of the substrate to improve the anchoring properties of the adhesive layer, etc. For example, if the anchoring properties of the adhesive layer to the substrate can be sufficiently improved by providing a primer coating or similar method on the first surface of the substrate, the reinforcing film can be manufactured by adhering the cured adhesive layer to the first surface of the substrate. Furthermore, the anchoring properties of the adhesive layer to the substrate can also be improved by selecting the material of the substrate and the composition of the adhesive. Furthermore, the anchoring properties of the adhesive layer to the substrate can be improved by applying a temperature higher than room temperature to the reinforcing film having an adhesive layer on the first surface of the substrate. The temperature applied to improve the anchoring properties can be, for example, around 35°C to 80°C, around 40°C to 70°C, or around 45°C to 60°C.

[0213] In the case where the reinforcing film disclosed herein is an adhesive sheet (i.e., a double-sided adhesive sheet with a substrate) having a first adhesive layer disposed on a first side of a substrate and a second adhesive layer disposed on a second side of the substrate, the first adhesive layer and the second adhesive layer may have the same or different compositions. When the compositions of the first adhesive layer and the second adhesive layer are different, this difference may be, for example, a difference in composition, structure (thickness, surface roughness, forming range, forming pattern, etc.). For example, the second adhesive layer may also be an adhesive layer that does not contain polymer (B). The initial adhesion force of the surface (adhesive surface) of the second adhesive layer relative to the aforementioned polyimide film can be less than 200 gf / 25 mm, or greater than 200 gf / 25 mm, for example, more than 500 gf / 25 mm, more than 800 gf / 25 mm, or more than 1000 gf / 25 mm.

[0214] <Reinforced membrane with release liner>

[0215] The reinforcing film disclosed herein can be in the form of an adhesive product in which the surface (adhesive surface) of the adhesive layer abuts against the release surface of the release liner. Therefore, according to this specification, a reinforcing film with a release liner, including any reinforcing film disclosed herein and a release liner having a release surface abutting against the adhesive surface of the reinforcing film, can be provided.

[0216] It should be noted that in this specification, "release liner" is also referred to as "release pad" and can include concepts such as release film or release sheet.

[0217] The thickness of the release liner is not particularly limited, but is typically suitable for a thickness of approximately 5 μm to 200 μm. If the thickness of the release liner is within this range, the adhesion and peeling performance of the adhesive layer are excellent, and therefore preferred. In some embodiments, the thickness of the release liner can be, for example, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. Furthermore, from the viewpoint of facilitating peeling from the adhesive layer, the thickness of the release liner can be, for example, 100 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, or 40 μm or less. Known antistatic treatments such as coating, compounding, or vapor deposition can also be applied to the release liner as needed.

[0218] There are no particular limitations on the release liner. For example, release liners with a release layer on the surface of the liner substrate, such as resin film or paper (which may be paper laminated with resins such as polyethylene), or release liners containing resin films made of low-adhesion materials such as fluoropolymers (polytetrafluoroethylene, etc.) or polyolefin resins (polyethylene, polypropylene, etc.) can be used. From the perspective of excellent surface smoothness, release liners with a release layer on the surface of the resin film used as the liner substrate, or release liners containing resin films made of low-adhesion materials, are preferred. As for the resin film, there are no particular limitations as long as it is a film that can protect the adhesive layer. Examples include: polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyester film (PET film, PBT film, etc.), polyurethane film, ethylene-vinyl acetate copolymer film, etc. In forming the aforementioned release layer, known release agents such as silicone-based release agents, long-chain alkyl-based release agents, olefin-based release agents, fluorinated release agents, fatty acid amide-based release agents, molybdenum sulfide, and silica powder can be used. Silicone-based release agents are particularly preferred.

[0219] There is no particular limitation on the thickness of the release layer, which is usually about 0.01 μm to 1 μm, preferably about 0.1 μm to 1 μm. There is no particular limitation on the method of forming the release layer, and known methods can be appropriately adopted depending on the type of release agent used.

[0220] <Uses>

[0221] The reinforcing film provided in this specification exhibits good reprocessability in the initial stage of application to the substrate, thus helping to suppress yield reduction and improve the quality of products containing the reinforcing film. Furthermore, after being applied to the substrate, the adhesive strength of the reinforcing film can be significantly increased through curing or heating. For example, by heating at an appropriate time after application to the substrate, the reinforcing film can be firmly bonded to the substrate. Utilizing these features, the reinforcing film disclosed herein can be preferably used in various fields for reinforcing components contained in various products.

[0222] The reinforcing film disclosed herein can preferably be in the form of an adhesive sheet with a substrate having an adhesive layer on at least the first side of a film-like substrate having a first side and a second side, and used as a reinforcing film to be bonded to an adherend for reinforcing the adherend. In this reinforcing film, a film substrate comprising a resin film as a base film is preferably used as the film substrate. Furthermore, from the viewpoint of improving reinforcing performance, the adhesive layer is preferably fixed to the first side of the film-like substrate.

[0223] For example, optical components used in optical products and electronic components used in electronic products are undergoing high integration, miniaturization, and thinning, potentially involving the stacking of multiple thin optical / electronic components with different coefficients of linear expansion and thicknesses. By attaching the reinforcing film described above to such components, appropriate rigidity can be imparted to them. Consequently, during the manufacturing process and / or in the finished product, curling and bending caused by stress that may arise between multiple components with different coefficients of linear expansion and thicknesses can be suppressed.

[0224] Furthermore, in the manufacturing process of optical / electronic products, when performing shape processing such as cutting on thin optical / electronic components as described above, attaching a reinforcing film to the component can alleviate localized stress concentration on the optical / electronic component during processing, reducing the risk of cracks, breakage, and peeling of laminated components. Attaching the aforementioned reinforcing film to the optical / electronic component as a reinforcing member can also help alleviate localized stress concentration during transport, stacking, and rotation of the component, and suppress bending and flexing caused by the component's own weight.

[0225] Furthermore, when optical products, electronic products, and other devices incorporating the aforementioned reinforcing film are used by consumers in the market, even in cases of unexpected stress such as dropping the device, placing it under heavy objects, or being struck by flying objects, the reinforcing film can mitigate the pressure exerted on the device. Therefore, by incorporating the reinforcing film into the aforementioned device, the durability of the device can be improved.

[0226] Furthermore, the reinforcing film disclosed herein is preferably used in a manner that involves attaching it to components constituting various portable devices. Here, "portable" is insufficient to simply mean "carryable"; it refers to a level of portability that allows a person (standard adult) to move it relatively easily. Examples of portable devices include mobile phones, smartphones, tablet PCs, laptop PCs, various wearable devices, digital cameras, digital camcorders, audio equipment (portable music players, IC recorders, etc.), calculators (desktop electronic calculators, etc.), portable gaming devices, electronic dictionaries, electronic notebooks, e-books, in-vehicle information devices, portable radios, portable televisions, portable printers, portable scanners, portable modems, and other portable electronic devices, as well as mechanical wristwatches, pocket watches, flashlights, hand mirrors, etc. Examples of components constituting the aforementioned portable electronic devices include optical films and display panels used in image display devices such as liquid crystal displays and film-type displays. The reinforcing film disclosed herein is also preferably used in a manner that involves attaching it to various components in automobiles, home appliances, etc.

[0227] Furthermore, the reinforcing film disclosed herein has an adhesive layer that exhibits good flexibility even in low-temperature regions. Therefore, taking advantage of this, it is preferably used in applications where it is adhered to components of devices comprising flexible elements (e.g., flexible displays, or flexible devices; also referred to as rollable or foldable devices). Examples of such devices include various portable devices as described above, and preferred examples include various portable electronic devices. Examples of components constituting such portable electronic devices include optical films used in image display devices such as liquid crystal displays and organic EL (electroluminescent) displays, and display panels. The reinforcing film disclosed herein is preferably used in such portable electronic devices for reinforcing components constituting the device (typically referred to as flexible devices, foldable devices, rollable devices, or image display devices).

[0228] Furthermore, the reinforcing film disclosed herein is suitable for reinforcing optical components used as constituent elements in liquid crystal display panels, plasma display panels (PDPs), organic EL displays, etc., during manufacturing, transportation, and use. The reinforcing film disclosed herein is useful, for example, as a reinforcing film for optical components such as polarizing plates (polarizing films), wavelength plates, phase retardation plates, optical compensation films, brightness enhancement films, light diffusers, and reflectors used in liquid crystal display panels.

[0229] It should be noted that the applications of the reinforcing membrane disclosed herein are not particularly limited, and it can be used for various applications aimed at imparting rigidity, impact resistance, etc. The reinforcing membrane disclosed herein is not only preferably used in flexible equipment applications as described above, but can also be used in other applications not involving flexible equipment. The reinforcing membrane possesses good adhesive properties (e.g., flexibility in low-temperature regions), meaning that the application range of the reinforcing membrane is less restricted, which is a significant practical advantage.

[0230] The matters disclosed in this specification include the following.

[0231] [1] A reinforcing membrane comprising an adhesive layer comprising a polymer (A) and a polymer (B), wherein the polymer (B) comprises monomer units having a polyorganosiloxane backbone and (meth)acrylic monomer units, and the polymer (A) is an acrylic polymer comprising monomer units derived from nitrogen-containing monomers, wherein the amount of the monomer units derived from nitrogen-containing monomers contained in 100 parts by weight of the polymer (A) is W N The [parts by weight] are 14 parts by weight or less, and the above adhesive layer further comprises W relative to 100 parts by weight of the above polymer (A). Zr [parts by weight] of zirconium-containing compounds, the above W N [Parts by weight] relative to the above W Zr The ratio of [parts by weight] (W) N / W Zr The value is 4 or higher.

[0232] [2] The reinforcing membrane according to [1] above, wherein the adhesive layer comprises a crosslinking agent.

[0233] [3] The reinforcing membrane according to [1] or [2] above, wherein the content of the polymer (B) in the adhesive layer is 0.1 to 10 parts by weight relative to 100 parts by weight of the polymer (A).

[0234] [4] The reinforcing membrane according to any one of [1] to [3] above, wherein the polymer (A) comprises a monomer unit derived from a monomer having a ring containing nitrogen atoms as the monomer unit derived from the nitrogen-containing monomer.

[0235] [5] The reinforcing film according to any one of [1] to [4] above, wherein the adhesive force N1 after being adhered to the polyimide film and subjected to 30 minutes at 23°C is 200gf / 25mm or less.

[0236] [6] The reinforcing film according to any one of [1] to [5] above, wherein the adhesive force N2 after being adhered to the polyimide film and heated at 60°C for 1 hour and then at 23°C for 30 minutes is 1000gf / 25mm or more.

[0237] [7] The reinforcing film according to any one of [1] to [6] above, wherein the rate of increase [%) of the adhesive force N2 [gf / 25mm] after being bonded to the polyimide film and heated at 60°C for 1 hour and then at 23°C for 30 minutes is 900% or more relative to the adhesive force N1 [gf / 25mm] after being bonded to the polyimide film and then at 23°C for 30 minutes.

[0238] [8] The reinforcing membrane according to any one of [1] to [7] above, wherein the adhesive constituting the adhesive layer has a storage modulus of 1000 kPa or less at -20°C.

[0239] [9] An optical component having a reinforcing film as described in any one of [1] to [8] above.

[0240]

[10] An electronic component having a reinforcing film as described in any one of [1] to [8] above.

[0241]

[11] An adhesive composition comprising a polymer (A) and a polymer (B), wherein the polymer (B) comprises monomer units having a polyorganosiloxane backbone and (meth)acrylic monomer units, and the polymer (A) is an acrylic polymer comprising monomer units derived from nitrogen-containing monomers, wherein 100 parts by weight of the polymer (A) comprises W... N The [parts by weight] are 14 parts by weight or less, and the above adhesive composition further comprises W parts by weight relative to 100 parts by weight of the above polymer (A). Zr [parts by weight] of zirconium-containing compounds, the above W N [Parts by weight] relative to the above W Zr The ratio of [parts by weight] (W) N / W Zr The value is 4 or higher.

[0242]

[12] An adhesive comprising a polymer (A) and a polymer (B), wherein the polymer (B) comprises monomer units having a polyorganosiloxane backbone and (meth)acrylic monomer units, and the polymer (A) is an acrylic polymer comprising monomer units derived from nitrogen-containing monomers, wherein 100 parts by weight of the polymer (A) contains W of the amount of the monomer units derived from nitrogen-containing monomers. N The [parts by weight] are 14 parts by weight or less, and the above adhesive also contains W parts by weight relative to 100 parts by weight of the above polymer (A). Zr [parts by weight] of zirconium-containing compounds, the above W N [Parts by weight] relative to the above W Zr The ratio of [parts by weight] (W) N / W Zr The value is 4 or higher.

[0243] Example

[0244] The following describes some embodiments related to the present invention, but it is not intended to limit the invention to the specific examples shown. It should be noted that, unless otherwise specified, "parts" and "%" in the following description refer to weight.

[0245] <Polymer Synthesis>

[0246] (Synthesis example A1)

[0247] A four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet tube, and condenser was filled with 89.3 parts of 2-ethylhexyl acrylate (2EHA), 8.9 parts of 4-hydroxybutyl acrylate (4HBA), 1.8 parts of N-vinylpyrrolidone (NVP), 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and ethyl acetate as a polymerization solvent. Nitrogen gas was introduced while stirring slowly, and the liquid temperature in the flask was maintained at approximately 65°C for 6 hours to prepare a polymer A1 solution with a polymer concentration of 35%. The weight-average molecular weight (Mw) of polymer A1 was 540,000.

[0248] (Synthesis Example A2)

[0249] The monomer composition was changed to 70 parts / 20 parts / 8 parts / 1 part / 0.6 parts of 2EHA / butyl acrylate (BA) / laurate acrylate (LA) / 4HBA / NVP. Otherwise, solution polymerization was carried out in the same manner as in synthesis example A1 to obtain a solution of polymer A2.

[0250] (Synthesis Example A3)

[0251] The monomer composition was changed to 63 parts / 9 parts / 13 parts / 15 parts of 2EHA / methyl methacrylate (MMA) / 2-hydroxyethyl acrylate (HEA) / NVP. Otherwise, solution polymerization was carried out in the same manner as in synthesis example A1 to obtain a solution of polymer A3.

[0252] (Synthesis Example A4)

[0253] The monomer composition was changed to 2EHA / 4HBA = 91 parts / 9 parts, and solution polymerization was carried out in the same manner as in synthesis example A1 to obtain a solution of polymer A4.

[0254] (Synthesis example B1)

[0255] 101.15 parts of ethyl acetate, 40 parts of MMA, 20 parts of n-butyl methacrylate (BMA), 20 parts of 2-ethylhexyl methacrylate (2EHMA), 8.7 parts of a methacrylate monomer with a functional group equivalent of 900 g / mol containing a polyorganosiloxane backbone (trade name: X-22-174ASX, manufactured by Shin-Etsu Chemical Co., Ltd.), 11.3 parts of a methacrylate monomer with a functional group equivalent of 4600 g / mol containing a polyorganosiloxane backbone (trade name: KF-2012, manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.8 parts of thioglycerol as a chain transfer agent were added to a four-necked flask equipped with a stirrer, thermometer, nitrogen inlet tube, condenser, and dropping funnel. Then, after stirring at 70°C under a nitrogen atmosphere for 30 minutes, 0.2 parts of AIBN as a thermal polymerization initiator were added, and the reaction was carried out at 70°C for 3 hours. Next, after stirring at 80°C for 30 minutes, 0.1 parts of AIBN were added, and the reaction was carried out at 80°C for 2 hours. Then, 0.05 parts of AIBN were added, and the reaction was carried out at 80°C for 2 hours to obtain polymer B1. The Mw of polymer B1 is 20000.

[0256] (Synthetic Examples B2 and B3)

[0257] The amount of chain transfer agent (thioglycerol) used was changed to 0.6 parts (Synthesis Example B2) or 1.5 parts (Synthesis Example B3) relative to 100 parts of monomer raw material. Otherwise, polymers B2 and B3 were prepared in the same manner as in Synthesis Example B1. The Mw of polymer B2 was 27,600, and the Mw of polymer B3 was 12,600.

[0258] (Synthesis Example B4)

[0259] The monomer composition was changed to MMA / BMA / 2EHMA / X-22-174ASX / KF-2012=40 / 20 / 20 / 3.2 / 16.8, and polymer B4 was prepared in the same manner as in synthesis example B1. The Mw of polymer B4 is 20000.

[0260] It should be noted that the Mw of each of the above polymers was determined using a GPC apparatus (TOSOH, HLC-8220GPC) under the following conditions and calculated using polystyrene conversion.

[0261] [GPC Conditions]

[0262] • Sample concentration: 0.2 wt% (tetrahydrofuran (THF) solution).

[0263] • Sample injection volume: 10 μL.

[0264] • Eluent: THF, Flow rate: 0.6 mL / min.

[0265] • Measurement temperature: 40℃.

[0266] • Chromatographic columns: Sample column; TSKguardcolumn SuperHZ-H (1 column) + TSKgel SuperHZM-H (2 columns); Reference column; TSKgel SuperH-RC (1 column).

[0267] • Detector: Differential refractometer (RI).

[0268] <Enhanced Membrane Fabrication>

[0269] (Example 1)

[0270] To a polymer A1 solution, relative to 100 parts of polymer A1 contained in the solution, 2.0 parts of polymer B1, 0.1 parts of isocyanate compound C1 (isocyanurate form of hexamethylene diisocyanate, trade name "CORONATE HX", manufactured by TOSOH) as a crosslinking agent (converted to solid content), and 0.1 parts of zirconium tetraacetylacetone (trade name "ZC150", manufactured by Matsumoto Fine Chemical Co.) as a Zr-containing compound were added, and the solution was diluted with ethyl acetate until the total solid content was 30%, thus obtaining the acrylic adhesive solution of this example.

[0271] The adhesive solution obtained above is applied to a 75 μm thick polyethylene terephthalate (PET) film (support substrate) having an untreated first side. The solvent is removed by drying at 130°C for 1 minute, thereby forming an adhesive layer with a thickness of 25 μm. The silicone-treated side of a 25 μm thick PET film (release liner) with one side treated with silicone is then bonded to the adhesive surface of this adhesive layer, and the film is cured at 25°C for 4 days. Thus, a reinforcing film (reinforcing film) comprising the support substrate and an adhesive layer fixedly laminated onto the support substrate is obtained, with a release liner bonded to the adhesive surface of the adhesive layer.

[0272] (Examples 2~7)

[0273] The amounts of polymer B1, isocyanate compound C1, and the Zr-containing compound relative to polymer A1 were set as shown in Table 1. Otherwise, acrylic adhesive solutions for each example were obtained in the same manner as in Example 1. Using these acrylic adhesive solutions, reinforcing films for each example were prepared in the same manner as in Example 1.

[0274] (Example 8)

[0275] Isocyanate compound C2 (trimethylolpropane adduct of isophthalic diisocyanate, trade name "TAKENATE D110N", manufactured by Mitsui Chemicals Co., Ltd.) was used instead of isocyanate compound C1, and otherwise, the acrylic adhesive solutions of each example were obtained in the same manner as in Example 1. Using these acrylic adhesive solutions, the reinforcing films of each example were prepared in the same manner as the reinforcing film of Example 1.

[0276] (Examples 9~11)

[0277] Polymers B2 to B4 were used to replace polymer B1, and otherwise, acrylic adhesive solutions for each example were obtained in the same manner as in Example 1. Using these acrylic adhesive solutions, reinforcing films for each example were prepared in the same manner as those for the reinforcing film in Example 1.

[0278] (Example 12)

[0279] Polymer A2 was used instead of polymer A1, and otherwise, the acrylic adhesive solution of this example was obtained in the same manner as in Example 1. Using the acrylic adhesive solution, the reinforcing film of this example was prepared in the same manner as the reinforcing film of Example 1.

[0280] (Example 13)

[0281] The amount of Zr-containing compound used was set as shown in Table 1. Otherwise, the acrylic adhesive solution of this example was obtained in the same manner as in Example 12. Using the acrylic adhesive solution, the reinforcing film of this example was prepared in the same manner as the reinforcing film of Example 1.

[0282] (Examples 14~17)

[0283] In Example 14, iron(III) acetylacetonate (trade name "NACEM Iron(III)", manufactured by Nippon Chemical Industry Co., Ltd.) was used; in Example 15, aluminum triacetylacetonate (trade name "AL3100", manufactured by Matsumoto Fine Chemical Co., Ltd.) was used; in Example 16, titanium tetraacetylacetonate (trade name "TC401", manufactured by Matsumoto Fine Chemical Co., Ltd.) was used; and in Example 17, dibutyltin dilaurate (IV) (trade name "OL-1", manufactured by Tokyo Fine Chemical Co., Ltd.) was used instead of the Zr-containing compound used in Example 1. Otherwise, the acrylic adhesive solutions for each example were obtained in the same manner as in Example 1. Using these acrylic adhesive solutions, the reinforcing films for each example were prepared in the same manner as the reinforcing film prepared in Example 1.

[0284] (Example 18)

[0285] The amount of Zr-containing compound used was set as shown in Table 1. Otherwise, the acrylic adhesive solution of this example was obtained in the same manner as in Example 1. Using the acrylic adhesive solution, the reinforcing film of this example was prepared in the same manner as the reinforcing film of Example 1.

[0286] (Example 19)

[0287] Polymer B1 was not used; otherwise, the acrylic adhesive solution of this example was obtained in the same manner as in Example 1. Using the acrylic adhesive solution, the reinforcing film of this example was prepared in the same manner as the reinforcing film of Example 1.

[0288] (Example 20)

[0289] Using polymer A3 instead of polymer A1 and setting the amount of isocyanate compound C2 as shown in Table 1, the acrylic adhesive solution of this example was obtained in the same manner as in Example 8. Using this acrylic adhesive solution, the reinforcing film of this example was prepared in the same manner as the reinforcing film of Example 1.

[0290] (Example 21)

[0291] Polymer A4 was used instead of polymer A1, and otherwise, the acrylic adhesive solution of this example was obtained in the same manner as in Example 1. Using the acrylic adhesive solution, the reinforcing film of this example was prepared in the same manner as the reinforcing film of Example 1.

[0292] <Evaluation>

[0293] Energy storage modulus at -20℃ (G') -20 )]

[0294] A 75 μm thick release liner R1 (trade name "DIAFOIL MRF75", manufactured by Mitsubishi Chemical Corporation), made of polyester resin and treated with silicone on one side, was prepared. An acrylic adhesive solution of various examples was applied to the silicone-treated side of R1 and dried at 130°C for 1 minute to form an adhesive layer with a thickness of 25 μm. Next, a 75 μm thick release liner R2 (trade name "DIAFOIL MRF75", manufactured by Mitsubishi Chemical Corporation), also treated with silicone on one side, was placed over the surface of the resulting adhesive layer with its silicone-treated side facing the adhesive layer. The layer was then cured at 50°C for 1 day.

[0295] Only the obtained adhesive layer is removed, stacked to a thickness of about 1 mm, and punched into φ8 mm cylindrical particles to be used as samples for testing.

[0296] The sample was fixed in a fixture with a φ8mm parallel plate, and the storage modulus (G') at -20°C was measured using a dynamic viscoelasticity measuring device (TA Instruments "DHR-2") under the following conditions. -20 [kPa].

[0297] Measurement mode: Shear mode.

[0298] Temperature range: -30℃ to 100℃.

[0299] • Heating rate: 5℃ / min.

[0300] • Frequency: 1Hz.

[0301] It should be noted that the storage modulus is equivalent to the portion of elastic energy stored when a material deforms, and is an indicator of the degree of hardness.

[0302] [Initial adhesion]

[0303] Each example of reinforcing film, along with the release liner, was cut into pieces 25 mm wide and 140 mm long, which were used as test samples. A 25 μm thick polyimide film (manufactured by Ube Industries, Ltd., trade name "UPILEX 25S") was fixed to a glass plate with double-sided tape (manufactured by Nitto Denko, trade name "No. 531"), thus preparing a polyimide plate for testing. The release liner was peeled off from the test sample to expose the adhesive surface, and a 2 kg hand roller was used to press it back and forth once to adhere it to the polyimide plate (the object to be adhered). After placing the test sample, which was thus pressed onto the substrate, at an ambient temperature of 23°C for 30 minutes, a tensile testing machine (manufactured by Shimadzu Corporation, trade name "Autograph AG-Xplus HS 6000mm / min high-speed mode (AG-50NXplus)") was used to measure the load when the reinforcing film was peeled from the substrate under the conditions of a peel angle of 180 degrees and a peel speed (tensile speed) of 300mm / min. The average load at the time of measurement was recorded as the initial adhesive force [gf / 25mm].

[0304] It should be noted that the initial adhesive strength of the reinforcing film in Example 19 was as high as 1000gf / 25mm or more, therefore the adhesive strength after heating and the rise rate were not measured.

[0305] [Adhesive strength after heating]

[0306] For each example of the reinforcing film, the test sample was prepared in the same manner as the initial adhesion test described above, and pressed onto the polyimide substrate (adhesive). Then, the test sample pressed onto the adhesive was heated at an ambient temperature of 60°C for 60 minutes. After that, it was placed at an ambient temperature of 23°C for 30 minutes, and the load when peeling the reinforcing film from the adhesive was measured using a tensile testing machine (Shimadzu Corporation, trade name "Autograph AG-Xplus HS 6000mm / min high-speed mode (AG-50NX plus)") at a peel angle of 180 degrees and a peel speed (tensile speed) of 300mm / min. The average load at the time of measurement was recorded as the adhesive force after heating [gf / 25mm].

[0307] [Rise Rate]

[0308] Based on the initial adhesive strength [gf / 25mm] and the adhesive strength [gf / 25mm] of the reinforcing film in each example, the rate of increase in adhesive strength is calculated according to the following formula.

[0309] Increase rate [%) = (Adhesive strength after heating [gf / 25mm] / Initial adhesive strength [gf / 25mm]) × 100

[0310] The evaluation results of the reinforcing films for each example are shown in Table 1. Table 1 also includes a summary of the composition of the adhesive layer for each example. It should be noted that the "N monomer content W" in Table 1... N "[parts]" refers to the amount W of monomer units derived from nitrogen-containing monomers contained in 100 parts of polymer (A) used in each example. N [Quantity]. Table 1 shows the "Metal Compound Amount W". Zr "[parts]" indicates the amount of metal compound used relative to 100 parts of polymer (A) in each example. For convenience, "W" is also used in examples where the metal compound is not Zr. Zr The expression “W” in Table 1. N / W Zr "W represents the amount of N-containing monomer W of the polymer (A) used in each example." N [parts] relative to the amount of metal compound W Zr The ratio of [parts]. Similarly, in Table 1, for convenience, the amount W of monomer units derived from nitrogen-containing monomers is... N Polymer A3 with more than 14 parts, and polymer A4 without monomer units derived from nitrogen-containing monomers, are also shown in the "Polymer (A)" column.

[0311] [Table 1]

[0312]

[0313] As shown in Table 1, the adhesives in Examples 1-13 comprise polymer (A), polymer (B), and a Zr-containing compound, wherein the W of polymer (A) is... N Less than 14 portions, and more than (W) N / W Zr The values ​​are 4 or higher. Compared with the reinforcing films of Examples 14-19 and 21, the reinforcing films of these examples better balance low initial adhesion and increased adhesion after heating. In addition, compared with the adhesive of Example 20, the adhesives of Examples 1-13 have a significantly lower storage modulus at -20°C, and in addition to balancing the aforementioned low initial adhesion and increased adhesion after heating, they also exhibit good flexibility.

[0314] More specifically, comparing Example 1, which uses a Zr-containing compound as the metal compound, with Examples 14-16, which use a Zr-free metal compound instead of the Zr-containing compound, it is evident that using a Zr-containing compound tends to increase the adhesive strength of polyimide after heating. Example 17, which uses a tin compound instead of the Zr-containing compound, shows high adhesive strength after heating compared to Examples 14-16, but also has high initial adhesive strength compared to Examples 14-16, resulting in a lower rate of increase in adhesive strength. Furthermore, comparing Examples 1-3 and Example 18, which use Zr-containing compounds, it is evident that if the ratio (W... N / W Zr If the strength is below 4, the adhesive strength decreases sharply after heating. The reinforcing film of Example 19, using an adhesive without polymer (B), has high initial adhesive strength. N The adhesive of Example 20, which contains more than 14 parts of polymer A3, has a high storage modulus at -20°C, while the adhesive of Example 21, which uses polymer A4, which does not contain monomer units derived from nitrogen-containing monomers, has low adhesion after heating.

[0315] The specific examples of the present invention have been described in detail above, but they are merely examples and do not limit the scope of the claims. The technology described in the claims includes solutions derived from various modifications and alterations of the specific examples illustrated above.

[0316] Explanation of reference numerals in the attached figures

[0317] 1, 2, 3: Reinforcing film; 10: Supporting substrate; 10A: First surface; 10B: Second surface; 21: Adhesive layer (first adhesive layer); 21A: Adhesive surface (first adhesive surface); 21B: Adhesive surface (second adhesive surface); 22: Adhesive layer (second adhesive layer); 22A: Adhesive surface (second adhesive surface); 31, 32: Release liner; 100, 200, 300: Reinforcing film with release liner.

Claims

1. A reinforcing membrane comprising an adhesive layer, The adhesive layer comprises polymer A and polymer B. The polymer B comprises monomer units having a polyorganosiloxane backbone and (meth)acrylic acid monomer units. Polymer A is an acrylic polymer containing monomer units derived from nitrogen-containing monomers. The amount W of monomer units derived from nitrogen-containing monomers contained in parts by weight of polymer A100 N Less than 14 parts by weight, W N The unit is parts by weight. The adhesive layer further comprises W parts by weight relative to the polymer A100. Zr The zirconium-containing compound, wherein W N Relative to the W Zr The ratio is W N / W Zr For a value of 4 or higher, W Zr The unit is parts by weight, W N The unit is parts by weight.

2. The reinforcing membrane according to claim 1, wherein, The adhesive layer contains a crosslinking agent.

3. The reinforcing membrane according to claim 1 or 2, wherein, The content of polymer B in the adhesive layer is 0.1 to 10 parts by weight relative to polymer A100.

4. The reinforcing membrane according to claim 1 or 2, wherein, The polymer A comprises monomer units derived from a monomer having a ring containing nitrogen atoms as the monomer units derived from the nitrogen-containing monomer.

5. The reinforcing membrane according to claim 1 or 2, wherein, The adhesion strength N1 after being bonded to a polyimide film and subjected to 30 minutes at 23°C is less than 200gf / 25mm.

6. The reinforcing membrane according to claim 5, wherein, The adhesion strength N2 after being bonded to a polyimide film and heated at 60°C for 1 hour and then at 23°C for 30 minutes is above 1000gf / 25mm.

7. The reinforcing membrane according to claim 6, wherein, The rate of increase of the adhesive force N2 relative to the adhesive force N1 is over 900%. The unit of adhesive force N2 is gf / 25mm, the unit of adhesive force N1 is gf / 25mm, and the unit of the rate of increase is %.

8. The reinforcing membrane according to claim 1 or 2, wherein, The adhesive constituting the adhesive layer has a storage modulus of less than 1000 kPa at -20°C.

9. An optical component having a reinforcing film as described in claim 1 or 2 bonded thereto.

10. An electronic component having a reinforcing film as described in claim 1 or 2 bonded thereto.

Citation Information

Patent Citations

  • Premixing device for gasious fuel

    JP1984051153A

  • JP1988066199A

  • Simple herpesvirus glycoprotein and production thereof

    JP1988066200A

  • Shared memory access device

    JP1988073458A

  • Alkailine zinc storage battery

    JP1988076271A